Beryllium Oxide Pedestal
By using high-purity BeO and its derivatives ceramic materials to adjust their microstructure and composition gradients, the problems of structural degradation and temperature unevenness in existing ceramic materials at high temperatures have been solved, and the high-temperature performance and fastening force have been significantly improved.
Patent Information
- Application Number
- JP2022509585
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-15
- Filing Date
- 2020-08-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-08-13
AI Technical Summary
Existing ceramic pedals have structural problems under high temperature conditions, such as decomposition, thermal and mechanical degradation, inconsistent temperature uniformity and insufficient fastening forces, which are difficult to meet the needs of high-temperature semiconductor manufacturing processes.
Use ceramic materials containing molybdenum lithium oxygen (BeO) and its derivatives to improve the high-temperature performance and fastening force of the material by adjusting the purity, microstructure and composition of BeO.
The structural stability, temperature uniformity and fastening force are greatly improved under high temperature conditions, and the degradation problems of traditional ceramic materials at high temperatures are avoided.
Smart Images

Figure 0007654636000004 
Figure 0007654636000005 
Figure 0007654636000006
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 887,282, filed August 15, 2019, the entire contents of which are incorporated herein by reference.
[0002]
[0002] The present disclosure relates to ceramic pedestals for high temperature applications. In particular, the present disclosure relates to pedestals comprising beryllium oxide for use in semiconductor manufacturing processes. [Background technology]
[0003]
[0003] In many high temperature substrate processing applications, a substrate is treated, e.g., etched, coated, cleaned, and / or its surface energy is activated, in a high temperature processing chamber. To perform the processing, a process gas is introduced into the processing chamber and then energized to achieve a plasma state. The energization can be performed by applying an RF voltage to an electrode, e.g., a cathode, and electrically grounding the anode to form a capacitive field in the processing chamber. The substrate is then treated by the plasma generated in the processing chamber to etch or deposit material thereon.
[0004]
[0004] During this process, the substrate must be supported (and held in place). Often, a ceramic pedestal is used to accomplish this goal. In some instances, an electrostatic chuck assembly (as part of the pedestal) is used to hold the substrate in place. Other support mechanisms, such as mechanical and vacuum, are also known. Electrostatic chucks often include an electrode covered by a dielectric. When the electrode is charged, an opposing electrostatic charge in the substrate and the resulting electrostatic force grips the substrate to the electrostatic chuck. Once the substrate is securely gripped by the chuck, plasma processing can proceed.
[0005]
[0005] Some known plasma processes are often carried out at relatively high temperatures and in highly corrosive gases. For example, etching of aluminum is carried out at temperatures between 100°C and 200°C, whereas etching of copper or platinum is carried out at temperatures between 250°C and 600°C. These temperatures and corrosive gases thermally degrade the materials used to manufacture the chuck. Conventional ceramic pedestals have used various oxides, nitrides, and alloys, such as aluminum nitride, aluminum oxide, silicon dioxide, silicon carbide, silicon nitride, sapphire, zirconia, or graphite, or anodized metals, as the primary components. In some cases, these requirements can be met by conventional ceramic materials, such as aluminum oxide or aluminum nitride.
[0006]
[0006] However, as technology advances, higher substrate processing operating conditions (temperatures) are desired, e.g., greater than 650° C., greater than 750° C., or even greater than 800° C. Unfortunately, it has been discovered that conventional ceramic pedestal materials suffer from structural problems, e.g., decomposition, thermal and / or mechanical degradation, shattering, and delamination, under such high temperatures.
[0007]
[0007] Additionally, conventional ceramic pedestals have been found to demonstrate inconsistent temperature uniformity across the pedestal plate surface during operation, possibly due to the inherent properties of aluminum nitride, silicon dioxide, or graphite. This in turn leads to problematic inconsistencies in the processing performed on semiconductor wafers. Attempts have been made to improve the temperature uniformity in conventional pedestal plates. However, these attempts have included more complex heating setups and control mechanisms, such as an increased number of heating zones and thermocouples, which adds cost and uncertainty to the formation process.
[0008]
[0008] Conventional non-beryllium pedestals also struggle to apply sufficient chucking force (clamping pressure) required to hold the wafer in place, especially at elevated temperatures. Conventional pedestals also suffer from problems associated with microfracture, surface shattering, (thermal) decomposition, and low permeability at elevated temperatures. Even at moderate temperatures, conventional pedestals have problems with unchucking time, possibly due to their large volume.
[0009]
[0009] Furthermore, many of the conventional pedestals use layered structures that rely on adhesive bonding, for example, using brazing materials, or laminated structures via diffusion bonding to secure the metal conductors in multiple (ceramic) layers. However, such laminated structures often suffer from recurring structural problems and delaminations resulting from the stresses of operation at high temperatures.
[0010]
[0010] It may also be desirable to cool the substrate quickly to maintain the substrate within a narrow temperature range or to clean the pedestal, substrate, or chamber. However, temperature fluctuations occur in the intense plasma due to conjugation of RF energy and variations in plasma ion density across the substrate. These temperature fluctuations can cause a rapid increase or decrease in the temperature of the substrate, requiring stabilization. It is therefore desirable to have a pedestal that requires little or no cooling during cleaning, e.g., can be cleaned at operating temperature and / or with little or no cleaning cycle time, advantageously improving process efficiency (by reducing / eliminating downtime).
[0011]
[0011] In view of conventional pedestal technology, a need exists for an improved pedestal assembly having improved performance, particularly at high temperatures, e.g., above 650°C, demonstrating, for example, reduced decomposition, reduced heat, reduced microfractures, and / or reduced mechanical degradation, improved temperature uniformity, and / or excellent clamping pressures while demonstrating no delamination. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a graph showing the thermal diffusivities of examples and comparative examples plotted over the temperature range of 0° C. to 900° C. [Diagram 2]
[0013] FIG. 2 is a graph showing the specific heats of the examples and comparative examples plotted over the temperature range of 0° C. to 900° C. [Diagram 3]
[0014] FIG. 3 is a graph showing the thermal conductivity of the examples and comparative examples plotted over the temperature range of 0° C. to 900° C. [Figure 4]
[0015] FIG. 4 is a graph showing the permeability of the examples and comparative examples plotted over the temperature range of 0° C. to 850° C. [Diagram 5]
[0016] FIG. 5 is a graph showing the bulk resistivities of the examples and comparative examples plotted over the temperature range of 0° C. to 850° C. [Figure 6]
[0017] FIG. 6 is a graph showing the bulk resistivities of the examples and comparative examples plotted over the temperature range of 0° C. to 850° C. Summary of the Invention
[0013]
[0018] In some embodiments, the present disclosure relates to a pedestal assembly comprising a shaft and a base plate, the shaft containing a first beryllium oxide composition containing beryllium oxide and (1 ppb-1000 ppm or 10 ppb-800 ppm) fluorine / fluoride ions, and the base plate containing a second beryllium oxide composition containing at least 95 wt% beryllium oxide and optional fluorine / fluoride ions. The base plate is capable of withstanding a clamping pressure of at least 133 kPa and / or a fluorine / fluoride content of 1×10 at 800° C. 5Demonstrates a bulk resistivity of greater than ohm-m. The first beryllium oxide composition may contain more fluorine / fluoride ions than the second beryllium oxide composition and may be processed to achieve the fluorine / fluoride ion concentration. The first beryllium oxide composition may further comprise less than 50 wt% magnesium oxide and less than 50 wt% ppm silicon dioxide and / or 1-50 wt% ppm alumina; 1 ppb-10000 ppm sulfite; and / or 1 ppb-1 wt% ppm boron, barium, sulfur, or lithium, or combinations thereof (including oxides, alloys, complexes, or allotropes, or combinations thereof). The first beryllium oxide composition may have average grain boundaries greater than 0.1 microns and / or an average grain size less than 100 microns. The second beryllium oxide composition may further comprise 1 ppb-10 wt% ppm magnesium oxide and 1 ppb-10 wt% ppm silicon dioxide and / or 1 ppb-10 wt% magnesium trisilicate and / or 1 ppb-1 wt% lithium oxide. The first beryllium oxide composition may comprise more magnesium oxide and / or magnesium trisilicate than the second beryllium oxide composition. The first beryllium oxide composition may comprise less than 75 wt% aluminum nitride, and / or the second beryllium oxide composition may comprise less than 5 wt% aluminum nitride. The first beryllium oxide composition may have a conductivity of less than 300 W / mK at room temperature and / or a theoretical density in the range of 90%-100%, and / or the second beryllium oxide composition may have a conductivity of less than 400 W / mK at room temperature. The base plate may have a temperature variation of less than ±3% when heated to a temperature above 700°C, and / or a thermal conductivity of less than 1×10 at 800°C. 4The base plate may have a bulk resistivity of greater than ohm-m, and / or may demonstrate a corrosion loss of less than 0.016 wt%, and / or a dielectric constant of less than 20, and / or a surface hardness of at least 50 Rockwell on a 45N scale, and / or a coefficient of thermal expansion in the range of 5-15 across the entire base plate, and / or the smallest lateral dimension of the base plate may have a flatness of at least 100 mm, and / or a camber of less than 50 microns over a distance of 300 mm. The base plate may further include a heating element encapsulated in the base plate and / or optionally a mesa having a height of less than 1 micron. The base plate may include less than two laminate layers, and / or no separate layers. The shaft may include a stub portion having a similar coefficient of thermal expansion.
[0014]
[0019] The present disclosure also relates to a base plate having an upper portion and a lower portion, the base plate comprising a beryllium oxide composition containing at least 95 wt% beryllium oxide and optional fluorine / fluoride ions, the base plate having a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and / or a decomposition change of less than 1 wt% at temperatures above 1600° C. and / or a temperature variation of less than ±3% when heated to temperatures above 700° C. and / or a thermal stability of less than 1×10 8 and / or a bulk resistivity of less than 0.016 wt. % and / or a corrosion loss of less than 0.016 wt. % and / or a dielectric constant of less than 20 and / or a surface hardness of at least 50 Rockwell on a 45 N scale and / or 1×10 at 800°C. 5The base plate may demonstrate a bulk resistivity of greater than ohm-m, and / or a coefficient of thermal expansion in the range of 5-15 across the base plate (the coefficient of thermal expansion may vary less than 25% from top to bottom), and / or a cleaning cycle time of less than 2 hours, and / or a temperature variation of less than ±3%. The base plate may comprise a beryllium oxide composition comprising 1 ppb-10 wt% ppm, e.g., 1 ppm-5 wt%, magnesium oxide, and 1 ppb-10 wt% ppm, e.g., 1 ppm-5 wt%, silicon dioxide, and / or 1 ppb-10 wt% ppm, e.g., 1 ppm-5 wt%, magnesium trisilicate. The base plate may not comprise a separate layer and may have a thermal conductivity gradient that decreases from top to bottom, and / or a resistivity gradient that decreases from top to bottom, and / or a purity gradient that decreases from top to bottom, and / or a theoretical density gradient that decreases from top to bottom, and / or a dielectric constant gradient that increases from top to bottom. The base plate may further include an optional heating element comprising niobium and / or platinum, an optional coiled and / or crimped heating element, and / or an antenna. The purity of the upper portion may be at least 0.4% higher than the purity of the lower portion.
[0015]
[0020] The present disclosure also relates to a base plate having a top and a bottom and comprising a beryllium oxide composition, wherein the base plate has a decreasing thermal conductivity gradient from top to bottom, and / or a decreasing resistivity gradient from top to bottom, and / or a decreasing purity gradient from top to bottom, and / or a decreasing theoretical density gradient from top to bottom, and / or an increasing dielectric constant gradient from top to bottom. The base plate may have a thermal conductivity of the top in the range of 125-400 W / mK and a thermal conductivity of the bottom in the range of 146 W / mK-218 W / mK when measured at room temperature, and / or a thermal conductivity of the top in the range of 25 W / mK-105 W / mK and a thermal conductivity of the bottom in the range of 1 W / mK-21 W / mK when measured at 800° C., optionally wherein the thermal conductivity of the top is at least 6% higher than the thermal conductivity of the bottom when measured at room temperature, and / or optionally wherein the thermal conductivity of the top is at least 6% higher than the thermal conductivity of the bottom when measured at 800° C. The purity of the top portion may be in the range of 99.0-99.9 and the purity of the bottom portion may be in the range of 95.0-99.5. The purity of the top portion may be at least 0.4% higher than the purity of the bottom portion. The theoretical density of the top portion may be in the range of 93%-100% and the theoretical density of the bottom portion may be in the range of 93%-100%. The theoretical density of the top portion may be at least 0.5% higher than the theoretical density of the bottom portion. The dielectric constant of the top portion may be in the range of 1-20 and the dielectric constant of the bottom portion may be in the range of 1-20. The base plate may not include a separate layer. The base plate may demonstrate the clamping pressure, temperature variation, and corrosion losses described above.
[0016]
[0021] The present disclosure also relates to a shaft for a pedestal assembly comprising a beryllium oxide composition containing beryllium oxide and (10 ppb-800 ppm) fluorine / fluoride ions. The beryllium oxide composition may have an average grain boundary greater than 0.1 microns, and / or an amorphous grain structure, and / or an average grain size less than 100 microns, and / or may demonstrate a thermal conductivity less than 300 W / mK at room temperature, and / or a theoretical density in the range of 90-100. The shaft may demonstrate an upper thermal conductivity in the range of 146 W / mK-218 W / mK and a lower thermal conductivity in the range of 1 W / mK-218 W / mK when measured at room temperature, and / or an upper thermal conductivity in the range of 1 W / mK-21 W / mK and a lower thermal conductivity in the range of 1 W / mK-21 W / mK when measured at 800° C., and the theoretical density of the upper may be at least 0.5% higher than the theoretical density of the lower. The beryllium oxide composition may include less than 75 wt% aluminum nitride. The first beryllium oxide composition may include 1 ppb to 1000 ppm fluorine / fluoride ions, and / or less than 50 wt% magnesium oxide, and / or less than 50 wt% ppm silicon dioxide, and / or 1 ppb to 50 wt% ppm alumina, and / or 1 ppb to 10000 ppm sulfite, and / or 1 ppb to 1 wt% ppm boron, barium, sulfur, or lithium, or combinations thereof (including oxides, alloys, complexes, or allotropes, or combinations thereof).
[0017]
[0022] The present disclosure also relates to a pedestal assembly including a shaft of any of the above-described embodiments and a base plate containing multiple layers (optionally with brazing material) bonded together and optional printed heating elements.
[0018]
[0023] The present disclosure also relates to a base plate having an upper portion and a lower portion and comprising a ceramic composition, wherein the base plate has a clamping pressure of at least 133 kPa, a temperature variation of less than ±3° C. when heated to a temperature above 700° C., and / or a thermal stability of less than 1×10 at 800° C. 8and / or a bulk resistivity of less than 0.016 wt%, and / or a corrosion loss of less than 0.016 wt%, and / or a dielectric constant of less than 20, and / or a surface hardness of at least 50 Rockwell on a 45 N scale, and / or a coefficient of thermal expansion in the range of 5 to 15 throughout the entire base plate.
[0019]
[0024] The present disclosure also relates to a method of manufacturing a base plate, comprising the steps of: providing a first BeO powder and a third BeO powder, forming a second powder from the first and third powders, forming a first (lower) region from the first powder, forming a second (middle) region from the second powder, and forming a third (upper) region from the third powder to form a base plate precursor, the second region being disposed between the first and third regions, optionally mixing the base plate precursor to bond the powders, optionally placing a heating element in one region and / or crimping the ends, cold forming the base plate precursor, and firing the base plate precursor to form the base plate. The first and third (and second) powders may comprise different grades of raw BeO.
[0020]
[0025] The present disclosure also relates to a method of manufacturing a pedestal shaft, the method including processing a beryllium oxide composition to achieve a fluorine / fluoride ion concentration in the range of 1 ppb to 1000 ppm fluorine / fluoride ion.
[0021]
[0026] The present disclosure also relates to a method of cleaning a contaminated pedestal assembly, comprising the steps of providing a pedestal assembly and a wafer with the wafer disposed on top of the pedestal assembly, heating the wafer to a temperature above 600° C., cooling the wafer to a cooling temperature by less than 100° C. (or not cooling at all), cleaning the plate at the cooling temperature, and optionally reheating the wafer to 600° C., where the cleaning cycle time from the cooling step to the reheating step is less than 2 hours. The cleaning cycle time may be in the range of 0 to 10 minutes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022]
[0027] As mentioned above, conventional pedestal assemblies are often used to support and hold semiconductor substrates in place during processing, e.g., chemical vapor deposition, etching, and the like. Typical ceramic pedestals have used various oxides, nitrides, and alloys, e.g., aluminum nitride, aluminum oxide, silicon dioxide, or graphite, as the primary components. And, these ceramic materials can meet the requirements of processing methods at moderate to high temperatures, e.g., temperatures below 650°C or below 600°C. However, as technology advances, higher substrate processing operating temperatures, e.g., temperatures above 650°C or even above 800°C, are desired. Unfortunately, conventional ceramic pedestal materials have been found to suffer from structural problems, e.g., decomposition, thermal and / or mechanical degradation, and delamination, at such high temperatures. In addition, conventional pedestal materials are known to have insufficient bulk resistivity. In some cases, the unsatisfactory resistivity leads to insufficient chucking / clamping force required to hold the wafer in place, especially at high temperatures.
[0023]
[0028] Further, conventional ceramic pedestals have been found to demonstrate inconsistent temperature uniformity across the pedestal plate surface, which leads to problematic inconsistencies in the processing performed on semiconductor wafers. In addition, many of the conventional layered pedestal structures have been found to suffer from structural problems and delamination that often result from the stresses of high temperature operation.
[0024]
[0029] The inventors have now discovered that the use of the disclosed beryllium oxide (BeO) compositions (having high purity levels and phase component contents) results in pedestal assemblies (or pedestal base plates and shaft components) that demonstrate a synergistic combination of high temperature performance and high chucking forces ("clamping pressures") that can be related to resistivity. Without wishing to be bound by theory, it is hypothesized that certain specific component combinations of the BeO compositions (in some cases, in the disclosed component concentrations), optionally in combination with certain processing parameters, result in advantageous microstructures, e.g., grain boundaries and grain sizes, in the BeO, which in turn result in a combination of high temperature performance and high clamping pressures. Also, without wishing to be bound by theory, the disclosed BeO compositions result in pedestal base plates with optimal (lesser) amounts of magnesium oxide, silicon dioxide, and / or magnesium trisilicate, which contribute to high bulk resistivity.
[0025]
[0030] Additionally, the inventors have discovered that some of the disclosed beryllium oxide (BeO) compositions (in some cases with the disclosed component concentrations), in combination with certain processing parameters, unexpectedly result in advantageous microstructures (discussed in more detail herein).
[0026]
[0031] Additionally, it has been discovered that the components of the BeO composition provide a low dielectric constant, which translates into low capacitance and thus improved non-chucking time delay. The BeO compositions of the present disclosure have also been discovered to demonstrate improved corrosion resistance, improved thermal effusivity, improved thermal diffusivity, improved thermal conductivity, improved specific heat, and lower thermal hysteresis, all of which contribute to the performance synergies disclosed herein.
[0027]
[0032] It has been discovered that conventional ceramic pedestals, such as those formed using aluminum nitride, aluminum oxide, silicon dioxide, silicon carbide, silicon nitride, sapphire, zirconia, anodized metals, or graphite as a primary component, are unable to provide high temperature performance or acceptable clamping pressures at such temperatures, i.e., the clamping pressure is lacking / reduced, especially at elevated temperatures.
[0028] Pedestal Assembly
[0033] Disclosed herein is a pedestal assembly. The pedestal assembly includes a base plate disposed on or atop a shaft. The shaft contains (and is formed from) a first BeO composition containing BeO and fluoride ions and / or fluorine. The base plate contains (and is formed from) a second BeO composition containing BeO (at a high purity level, such as at least 95.0 wt%) and optional fluoride ions and / or fluorine. The BeO in the composition of the present disclosure is, in some embodiments, synthetic BeO, e.g., BeO manufactured from raw material (powder), as opposed to the solid natural BeO present in nature. The inventors have determined that the use of beryllium oxide (and optionally other components described herein) as a major component in the composition results in or contributes to the performance characteristics described herein, e.g., high temperature performance and / or superior clamping pressure.
[0029]
[0034] In some embodiments, the pedestal assembly (or its base plate) of the present disclosure demonstrates a wide range of clamping pressure capabilities. In some cases, the pedestal assembly of the present disclosure is a Johnsen-Rahbek pedestal. For example, the pedestal assembly of the present disclosure can demonstrate a clamping pressure of more than 133 kPa, e.g., more than 135 kPa, more than 140 kPa, more than 145 kPa, or more than 150 kPa. On the upper end, the pedestal assembly can demonstrate a clamping pressure of less than 160 kPa, e.g., less than 155 kPa, less than 150 kPa, less than 145 kPa, less than 140 kPa, or less than 135 kPa. In terms of range, the pedestal assembly may demonstrate a clamping pressure in the range of 133 kPa to 160 kPa, e.g., 133 kPa to 155 kPa, 133 kPa to 150 kPa, 135 kPa to 150 kPa, 135 kPa to 145 kPa, or 138 kPa to 143 kPa.
[0030]
[0035] As used herein, the terms "greater than," "less than," etc. are considered to include real number limits, e.g., interpreted as "greater than or equal to." Ranges are considered to include the endpoint values.
[0036] In other cases, the pedestal assembly of the present disclosure is a coulombic pedestal. For example, the pedestal assembly of the present disclosure may demonstrate a clamping pressure of more than 0.1 kPa, e.g., more than 0.5 kPa, more than 1 kPa, more than 1.3 kPa, more than 2 kPa, or more than 4 kPa. In terms of upper limits, the pedestal assembly may demonstrate a clamping pressure of less than 15 kPa, e.g., less than 14 kPa, less than 13 kPa, less than 12 kPa, or less than 10 kPa. In terms of ranges, the pedestal assembly may demonstrate a clamping pressure in the range of 0.1 kPa to 15 kPa, e.g., 0.5 kPa to 14 kPa, 1 kPa to 14 kPa, 1.3 kPa to 13 kPa, 2 kPa to 12 kPa, or 4 kPa to 10 kPa.
[0031]
[0037] In other cases, the pedestal assembly of the present disclosure is a partial Johnsen-Rahbek / partial Coulomb pedestal. For example, the pedestal assembly of the present disclosure may demonstrate a clamping pressure of more than 0.1 kPa, e.g., more than 1 kPa, more than 10 kPa, more than 13 kPa, more than 20 kPa, more than 40 kPa, or more than 60 kPa. In terms of upper limits, the pedestal assembly may demonstrate a clamping pressure of less than 160 kPa, e.g., less than 155 kPa, less than 135 kPa, less than 133 kPa, less than 130 kPa, less than 120 kPa, less than 100 kPa, or less than 80 kPa. In terms of range, the pedestal assembly can demonstrate a clamping pressure in the range of 0.1 kPa to 160 kPa, e.g., 1 kPa to 155 kPa, 1 kPa to 135 kPa, 1 kPa to 133 kPa, 10 kPa to 130 kPa, 13 kPa to 133 kPa, 20 kPa to 120 kPa, 40 kPa to 100 kPa, or 60 kPa to 80 kPa.
[0032]
[0038] In some embodiments, the pedestal assembly of the present disclosure can demonstrate a clamping pressure of more than 0.1 kPa, e.g., more than 1 kPa, more than 1.3 kPa, more than 3 kPa, more than 5 kPa, more than 10 kPa, or more than 20 kPa. In terms of upper limits, the pedestal assembly can demonstrate a clamping pressure of less than 70 kPa, e.g., less than 60 kPa, less than 55 kPa, less than 50 kPa, or less than 45 kPa. In terms of ranges, the pedestal assembly can demonstrate a clamping pressure in the range of 0.1 kPa to 70 kPa, e.g., 1 kPa to 60 kPa, 1.3 kPa to 55 kPa, 5 kPa to 50 kPa, or 10 kPa to 45 kPa.
[0033]
[0039] In some embodiments, the pedestal assembly of the present disclosure can demonstrate a clamping pressure of more than 70 kPa, e.g., more than 100 kPa, more than 135 kPa, more than 150 kPa, more than 200 kPa, or more than 250 kPa. In terms of upper limits, the pedestal assembly can demonstrate a clamping pressure of less than 550 kPa, e.g., less than 500 kPa, less than 450 kPa, less than 400 kPa, or less than 350 kPa. In terms of ranges, the pedestal assembly can demonstrate a clamping pressure in the range of 70 kPa to 550 kPa, e.g., 100 kPa to 500 kPa, 135 kPa to 450 kPa, 150 kPa to 400 kPa, 200 kPa to 400 kPa, or 250 kPa to 350 kPa.
[0034]
[0040] In addition, it has been discovered that certain compositions and processing parameters result in property gradients throughout the thickness of the pedestal base plate and / or the length of the pedestal shaft. Beneficially, it has been discovered that these gradients better distribute the thermal and mechanical stresses present in high temperature deposition operations, which can eliminate stress risers. Importantly, these gradients are achieved without the need for separate layers.
[0035]
[0041] The pedestal assemblies of the present disclosure are surprisingly capable of achieving the aforementioned clamping pressures under more severe operating conditions (compared to conventional pedestal assemblies), e.g., temperature, pressure, and / or voltage. In some embodiments, the pedestal is capable of achieving the aforementioned clamping pressures at temperatures greater than 400° C., e.g., greater than 500° C., greater than 600° C., greater than 700° C., or greater than 800° C., and / or voltages greater than 300 V, e.g., greater than 400 V, greater than 450 V, greater than 500 V, greater than 550 V, greater than 600 V, or greater than 650 V. In contrast, conventional aluminum nitride pedestals have been found to be highly ineffective at clamping under harsh operating conditions, and in most cases, conventional aluminum nitride decomposes under these conditions, resulting in limited (if any) clamping capability.
[0036] shaft
[0042] The present disclosure also relates to a shaft. The shaft comprises a BeO composition, for example the first BeO composition described above. Due to the composition and optional processing thereof, the shaft demonstrates excellent performance characteristics and microstructures disclosed herein. In particular, the shaft has an average grain boundary or amorphous grain structure of greater than 0.1 microns as described herein. In some cases, the shaft has advantageous property gradients over the length of the shaft (see below).
[0037]
[0043] The first BeO composition includes BeO as a major component. The BeO may be present in an amount ranging from 50 wt% to 99.9 wt%, for example, from 75 wt% to 99.9 wt%, from 85 wt% to 99.7 wt%, from 90 wt% to 99.7 wt%, or from 92 wt% to 99.5 wt%. In terms of lower limits, the first BeO composition may include more than 50 wt% BeO, for example, more than 75 wt%, more than 85 wt%, more than 90 wt%, more than 92 wt%, more than 95 wt%, more than 98 wt%, or more than 99 wt% BeO. In terms of an upper limit, the first BeO composition may include less than 99.9 wt% BeO, e.g., less than 99.8 wt%, less than 99.7 wt%, less than 99.6 wt%, less than 99.5 wt%, or less than 99.0 wt% BeO.
[0038]
[0044] In some embodiments, the first BeO composition, e.g., the BeO composition of the shaft, comprises 1 ppb to 1000 ppm of fluoride ions and / or fluorine, e.g., 10 ppb to 800 ppm, 100 ppb to 500 ppm, 500 ppb to 500 ppm, 1 ppm to 300 ppm, 25 ppm to 250 ppm, 25 ppm to 200 ppm, 50 ppm to 150 ppm, or 75 ppm to 125 ppm of fluoride ions and / or fluorine. In terms of lower limits, the first BeO composition may comprise more than 1 ppb of fluoride ions and / or fluorine, e.g., more than 10 ppb, more than 100 ppb, more than 500 ppb, more than 1 ppm, more than 2 ppm, more than 50 ppm, or more than 75 ppm of fluoride ions and / or fluorine. With respect to the upper limit, the first BeO composition may contain less than 1000 ppm of fluoride ions and / or fluorine, e.g., less than 800 ppm, less than 500 ppm, less than 300 ppm, less than 250 ppm, less than 200 ppm, less than 150 ppm, or less than 125 ppm of fluoride ions and / or fluorine. In some embodiments, the first BeO composition is processed to achieve a fluorine / fluoride ion concentration, e.g., by performing a separation operation to reach a desired fluorine / fluoride ion concentration. In some cases, the desired fluorine / fluoride ion concentration does not occur naturally and requires such a separation operation. Furthermore, it has been discovered that the disclosed amount of fluorine / fluoride ions in the BeO composition surprisingly provides unexpected benefits. It is believed that the fluorine / fluoride ions (optionally in the disclosed amount) surprisingly contribute / lead to a microstructure that is effective in disrupting phonon wave functions, phonon transport, and / or transmission (via scattering).
[0039]
[0045] In some embodiments, the first BeO composition contains more fluoride ions and / or fluorine than the second BeO composition. The inventors have surprisingly discovered that the difference in fluoride ion and / or fluorine content from the base plate to the shaft is important for at least the aforementioned phonon disruption properties. In some embodiments, the first BeO composition contains at least 10%, e.g., at least 20%, at least 30%, at least 50%, at least 75%, or at least 100% more fluoride ions and / or fluorine than the second BeO composition.
[0040]
[0046] In some cases, the first BeO composition further comprises magnesium oxide. For example, the first BeO composition may comprise 1 ppb to 50 wt% ppm of magnesium oxide, e.g., 100 ppm to 25 wt%, 500 ppm to 10 wt%, 0.1 wt% to 10 wt%, 0.5 wt% to 8 wt%, 0.5 wt% to 5 wt%, 0.7 wt% to 4 wt%, or 0.5 wt% to 3.5 wt% of magnesium oxide. In terms of lower limits, the first BeO composition may comprise more than 1 ppb of magnesium oxide, e.g., more than 10 ppb, more than 100 ppm, more than 500 ppm, more than 0.1 wt%, more than 0.5 wt%, more than 0.7 wt%, or more than 1 wt% of magnesium oxide. In terms of upper limits, the first BeO composition may include less than 50 wt% magnesium oxide, such as less than 25 wt%, less than 10 wt%, less than 8 wt%, less than 5 wt%, less than 4 wt%, or less than 3.5 wt% magnesium oxide.
[0041]
[0047] In some specific embodiments, the first BeO composition includes silicon dioxide. For example, the first BeO composition may include 1 ppb to 50 wt% ppm of silicon dioxide, such as 100 ppm to 25 wt%, 500 ppm to 10 wt%, 0.1 wt% to 10 wt%, 0.5 wt% to 8 wt%, 0.5 wt% to 5 wt%, 0.7 wt% to 4 wt%, or 0.5 wt% to 3.5 wt% of silicon dioxide. In terms of lower limits, the first BeO composition may include more than 1 ppb of silicon dioxide, such as more than 10 ppb, more than 100 ppm, more than 500 ppm, more than 0.1 wt%, more than 0.5 wt%, more than 0.7 wt%, or more than 1 wt% of silicon dioxide. In terms of upper limits, the first BeO composition may include less than 50 wt% silicon dioxide, e.g., less than 25 wt%, less than 10 wt%, less than 8 wt%, less than 5 wt%, less than 4 wt%, or less than 3.5 wt% silicon dioxide.
[0042]
[0048] The first BeO composition may include magnesium trisilicate. For example, the first BeO composition may include 1 ppb to 5 wt% magnesium trisilicate, such as 1 ppm to 2 wt%, 100 ppm to 2 wt%, 500 ppm to 1.5 wt%, 1000 ppm to 1 wt%, 2000 ppm to 8000 ppm, 3000 ppm to 7000 ppm, or 4000 ppm to 6000 ppm magnesium trisilicate. In terms of the lower limit, the first BeO composition may include more than 1 ppb magnesium trisilicate, such as more than 1 ppm, more than 100 ppm, more than 500 ppm, more than 1000 ppm, more than 2000 ppm, more than 3000 ppm, or more than 4000 ppm magnesium trisilicate. In terms of upper limits, the first BeO composition may include less than 5 wt.% magnesium trisilicate, e.g., less than 2 wt.%, less than 1.5 wt.%, less than 1 wt.%, less than 8000 ppm, less than 7000 ppm, or less than 6000 ppm magnesium trisilicate.
[0043]
[0049] In some cases, the first BeO composition further comprises alumina. For example, the first BeO composition may comprise 1 ppb to 50 wt% ppm of alumina, e.g., 100 ppm to 25 wt%, 500 ppm to 10 wt%, 0.1 wt% to 10 wt%, 0.5 wt% to 8 wt%, 0.5 wt% to 5 wt%, 0.7 wt% to 4 wt%, or 0.5 wt% to 3.5 wt% of alumina. In terms of lower limits, the first BeO composition may comprise more than 1 ppb of alumina, e.g., more than 10 ppb, more than 100 ppm, more than 500 ppm, more than 0.1 wt%, more than 0.5 wt%, more than 0.7 wt%, or more than 1 wt% of alumina. In terms of upper limits, the first BeO composition may include less than 50 wt% alumina, such as less than 25 wt%, less than 10 wt%, less than 8 wt%, less than 5 wt%, less than 4 wt%, or less than 3.5 wt% alumina.
[0044]
[0050] In some cases, the first BeO composition further comprises sulfite. For example, the first BeO composition may comprise 1 ppb to 10000 ppm of sulfite, e.g., 1 ppm to 5000 ppm, 1 ppm to 2000 ppm, 10 ppm to 1500 ppm, 10 ppm to 1000 ppm, 10 ppm to 500 ppm, 25 ppm to 200 ppm, or 50 ppm to 150 ppm of sulfite. In terms of the lower limit, the first BeO composition may comprise more than 1 ppb of sulfite, e.g., more than 1 ppm, more than 10 ppm, more than 25 ppm, or more than 50 ppm of sulfite. In terms of upper limits, the first BeO composition may contain less than 10,000 ppm sulfite, e.g., less than 5,000 ppm, less than 2,000 ppm, less than 1,500 ppm, less than 1,000 ppm, less than 500 ppm, less than 300 ppm, less than 200 ppm, or less than 150 ppm sulfite.
[0045]
[0051] In some cases, the first BeO composition includes a small amount of non-BeO ceramics, e.g., oxide ceramics. For example, the first beryllium oxide composition may include less than 75 wt% non-BeO ceramics, e.g., less than 50 wt%, less than 25 wt%, less than 10 wt%, less than 5 wt%, or less than 1 wt% non-BeO ceramics. In terms of ranges, the first BeO composition may include between 1 wt% and 75 wt%, e.g., between 5 wt% and 50 wt%, between 5 wt% and 25 wt%, or between 1 and 10 wt% non-BeO ceramics.
[0046]
[0052] The first BeO composition may further include other components, such as boron, barium, sulfur, or lithium, or combinations thereof (including oxides, alloys, composites, or allotropes, or combinations thereof). The first BeO composition may include these components in amounts ranging from 1 ppb to 1 wt% ppm, e.g., 10 ppb to 0.5 wt%, 10 ppb to 1000 ppm, 10 ppb to 900 ppm, 50 ppb to 800 ppm, 500 ppb to 1000 ppm, 1 ppm to 600 ppm, 50 ppm to 500 ppm, 50 ppm to 250 ppm, or 50 ppm to 150 ppm. In terms of lower limits, the first BeO composition may contain more than 1 ppb, e.g., more than 10 ppm, more than 50 ppb, more than 100 ppb, more than 500 ppb, more than 1 ppm, more than 50 ppm, more than 100 ppm, or more than 200 ppm, of these components. In terms of upper limits, the first BeO composition may contain less than 1 wt. %, e.g., less than 0.5 wt. %, less than 1000 ppm, less than 900 ppm, less than 800 ppm, less than 700 ppm, less than 600 ppm, less than 500 ppm, less than 250 ppm, or less than 150 ppm, of these components.
[0047]
[0053] In some embodiments, the first BeO composition includes less than 75 wt%, e.g., less than 50 wt%, less than 25 wt%, less than 10 wt%, less than 5 wt%, less than 3 wt%, or less than 1 wt% non-BeO ceramics, e.g., aluminum nitride. In terms of ranges, the first BeO composition may include 0.01 wt% to 75 wt%, e.g., 0.05 wt% to 50 wt%, 0.05 wt% to 25 wt%, or 0.1 to 10 wt% non-BeO ceramics.
[0048]
[0054] Other components may also be present, such as aluminum (other than the alumina described above), lanthanum, magnesium (other than the magnesium oxide or magnesium trisilicate described above), silicon (other than the silicon dioxide and magnesium trisilicate described above), or yttria or combinations thereof (including oxides, alloys, composites, or allotropes, or combinations thereof), and the above ranges and limits are applicable to these additional components.
[0049] Second Phase
[0055] In some cases, the shaft and / or base plate include a primary phase (first phase) and a secondary phase (second phase). The primary phase includes material particles, and the secondary phase includes material that forms grain boundaries, e.g., material between the particles. The compositions of the primary and secondary phases may differ from each other. The respective compositions of the secondary phases in the shaft and base plate may affect their performance characteristics, e.g., thermal conductivity, (theoretical) density, and especially their ability to scatter phonons. In general, the secondary phase is a relatively small part of the overall composition of the shaft and / or base plate. In some cases, the shaft contains, e.g., at least 5%, at least 10%, at least 25%, or at least 50% more secondary phase than the base plate, contributing to improved performance of the assembly.
[0050]
[0056] In some embodiments, the shaft comprises between 0.001 wt% and 50 wt% of the second phase, e.g., between 0.01 wt% and 25 wt%, between 0.01 wt% and 10 wt%, between 0.05 wt% and 10 wt%, between 0.1 wt% and 10 wt%, between 0.1 wt% and 5 wt%, between 0.5 wt% and 5 wt%, or between 0.5 wt% and 3 wt% of the second phase. In terms of upper limits, the shaft may comprise less than 50 wt% of the second phase, e.g., less than 25 wt%, less than 10 wt%, less than 5 wt%, less than 3 wt%, or less than 2 wt% of the second phase. In terms of lower limits, the shaft may contain more than 0.001 wt% of the second phase, e.g., more than 0.01 wt%, more than 0.05 wt%, more than 0.1 wt%, more than 0.5 wt%, or more than 1 wt% of the second phase. The weight percentages are based on the total weight of the shaft.
[0051]
[0057] In some embodiments, the base plate comprises 0.05 wt% to 10 wt% of the second phase, e.g., 0.05 wt% to 5 wt%, 0.1 wt% to 5 wt%, 0.1 wt% to 3 wt%, or 0.1 wt% to 1 wt% of the second phase. In terms of upper limits, the base plate may comprise less than 10 wt% of the second phase, e.g., less than 5 wt%, less than 3 wt%, less than 2 wt%, or less than 1 wt% of the second phase. In terms of lower limits, the base plate may comprise more than 0.05 wt% of the second phase, e.g., more than 0.1 wt%, more than 0.2 wt%, more than 0.5 wt%, more than 0.7 wt%, or more than 1 wt% of the second phase. The weight percentages are based on the total weight of the base plate.
[0052]
[0058] In some cases, the second phase may include a non-BeO component. For example, the second phase of the first BeO composition that constitutes the shaft may include magnesia (MgO), silica (SiO2), alumina, yttria, titania, lithia, lanthana, or magnesium trisilicate, or a mixture thereof. The first BeO composition (and the shaft made therefrom) includes non-BeO components, each of which may be present in an amount ranging from 1 ppb to 500 ppm, e.g., 500 ppb to 500 ppm, 1 ppm to 300 ppm, 1 ppm to 200 ppm, 10 ppm to 200 ppm, 50 ppm to 150 ppm, or 75 ppm to 125 ppm. In terms of upper limits, the first BeO composition may include non-BeO components, each present in an amount less than 500 ppm, e.g., less than 300 ppm, less than 200 ppm, less than 150 ppm, or less than 125 ppm. In terms of lower limits, the first BeO composition may include non-BeO components, each present in an amount greater than 1 ppb, e.g., greater than 500 ppb, greater than 1 ppm, greater than 10 ppm, greater than 25 ppm, greater than 50 ppm, greater than 75 ppm, or greater than 100 ppm. These weight percentages are based on the total weight of the first BeO composition, e.g., the total weight of the shaft.
[0053]
[0059] In some particular embodiments, the first BeO composition comprises between 1 ppb and 10,000 ppm, e.g., between 100 ppm and 9,000 ppm, between 2,000 ppm and 10,000 ppm, between 5,000 ppm and 10,000 ppm, between 5,000 ppm and 9,000 ppm, between 6,000 ppm and 9,000 ppm, or between 7,000 ppm and 8,000 ppm. In terms of lower limits, the first BeO composition may comprise more than 1 ppb, e.g., more than 10 ppb, more than 100 ppb, more than 1 ppm, more than 50 ppm, more than 100 ppm, more than 200 ppm, more than 1000 ppm, more than 2000 ppm, more than 3,000 ppm, more than 4,000 ppm, more than 5,000 ppm, more than 6,000 ppm, or more than 7,000 ppm of second phase magnesium oxide. In terms of upper limits, the first BeO composition may contain less than 10000 ppm, e.g., less than 9000 ppm, less than 8000 ppm, less than 7000 ppm, less than 6000 ppm, less than 5000 ppm, or less than 4000 ppm of second phase magnesium oxide.
[0054]
[0060] In some specific embodiments, the first BeO composition comprises from 1 ppb to 5000 ppm, e.g., from 100 ppb to 1000 ppm, from 100 ppb to 500 ppm, from 1 ppm to 500 ppm, from 1 ppm to 100 ppm, from 5 ppm to 50 ppm, from 1 ppm to 20 ppm, or from 2 ppm to 10 ppm of second phase silicon dioxide. In terms of lower limits, the first BeO composition comprises more than 1 ppb, e.g., more than 10 ppb, more than 100 ppb, more than 200 ppb, more than 500 ppb, more than 1 ppm, more than 2 ppm, more than 5 ppm, or more than 7 ppm of second phase silicon dioxide. In terms of upper limits, the first BeO composition contains less than 5000 ppm, e.g., less than 1000 ppm, less than 500 ppm, less than 100 ppm, less than 50 ppm, less than 20 ppm, or less than 10 ppm, of second phase silicon dioxide.
[0055]
[0061] In some specific embodiments, the first BeO composition comprises between 1 ppb and 5000 ppm, e.g., between 100 ppb and 1000 ppm, between 100 ppb and 500 ppm, between 1 ppm and 500 ppm, between 1 ppm and 100 ppm, between 5 ppm and 50 ppm, between 1 ppm and 2 ppm, or between 2 ppm and 10 ppm of second phase alumina. In terms of lower limits, the first BeO composition comprises more than 1 ppb, e.g., more than 10 ppb, more than 100 ppb, more than 200 ppb, more than 500 ppb, more than 1 ppm, more than 2 ppm, more than 5 ppm, or more than 7 ppm of second phase alumina. In terms of upper limits, the first BeO composition contains less than 5000 ppm, eg, less than 1000 ppm, less than 500 ppm, less than 100 ppm, less than 50 ppm, less than 20 ppm, or less than 10 ppm of second phase alumina.
[0056]
[0062] The second phase of the first BeO composition may further include other components such as carbon, calcium, cerium, iron, hafnium, molybdenum, selenium, titanium, yttrium, or zirconium, or combinations thereof (including oxides, alloys, composites, or allotropes, or combinations thereof). These components may also be present in the first phase of the first BeO composition (and in the shaft). For example, the first BeO composition may include these components in amounts ranging from 1 ppb to 5 wt%, e.g., 10 ppb to 3 wt%, 100 ppb to 1 wt%, 1 ppm to 1 wt%, 1 ppm to 5000 ppm, 10 ppm to 1000 ppm, 50 ppm to 500 ppm, or 50 ppm to 300 ppm. On the upper end, these components may be present in amounts less than 5 wt%, e.g., less than 3 wt%, less than 1 wt%, less than 5000 ppm, less than 1000 ppm, less than 500 ppm, or less than 300 ppm. On the lower end, these components may be present in amounts greater than 1 ppb, e.g., greater than 10 ppb, greater than 100 ppb, greater than 1 ppm, greater than 10 ppm, or greater than 50 ppm.
[0057]
[0063] It has been discovered that the particular composition of the first BeO composition, optionally in conjunction with its processing, results in a specific microstructure that is particularly beneficial for high temperature performance. Without being bound by theory, it is hypothesized that magnesium oxide, silicon dioxide, and / or magnesium trisilicate unexpectedly increase grain boundaries and / or reduce grain size, creating a more thermally restrictive barrier between the grains, e.g., providing a barrier choke between the grains. This improved microstructure is believed to contribute to improved high temperature performance. In some embodiments, the first BeO composition has an average grain boundary of more than 0.05 microns, e.g., more than 0.07 microns, more than 0.09 microns, more than 0.1 microns, more than 0.3 microns, more than 0.5 microns, more than 0.7 microns, more than 1.0 microns, more than 2 microns, more than 4 microns, more than 5 microns, more than 7 microns, or more than 10 microns. In terms of ranges, the first BeO composition has an average grain boundary in the range of 0.05 microns to 25 microns, e.g., 0.05 microns to 15 microns, 0.07 microns to 12 microns, 0.1 microns to 10 microns, 0.5 microns to 10 microns, or 1 micron to 7 microns. In addition to magnesium oxide, silicon dioxide, and / or magnesium trisilicate, it is envisioned that other minor components disclosed herein may further beneficially contribute to the improvement, although perhaps not to the same extent.
[0058]
[0064] In some embodiments, the BeO composition has an average particle size of less than 100 microns, e.g., less than 90 microns, less than 75 microns, less than 60 microns, less than 50 microns, less than 40 microns, less than 35 microns, less than 25 microns, less than 15 microns, less than 10 microns, or less than 5 microns. In terms of range, the BeO composition may have an average particle size ranging from 0.1 microns to 100 microns, e.g., 1 micron to 75 microns, 1 micron to 35 microns, 3 microns to 25 microns, or 5 microns to 15 microns. It has been discovered that this smaller particle size beneficially prevents heat transfer and thus contributes to or enhances high temperature performance, limiting the transfer of heat from the plate to the opposite end of the shaft, causing the base plate and adjacent end of the shaft to remain hot, while the opposite end of the shaft (the side away from the base plate) remains cool. It is envisioned that the particular particle size also has a beneficial effect on phonon scattering.
[0059]
[0065] In some cases, the shaft includes a "stub" section (thermal choke section). The stub section may be a ring or washer in some cases. The stub section may be used to moderate the shaft temperature. The coefficient of thermal expansion is, for example, within 25%, 20%, 15%, 10%, 5%, 3%, or 1% of the remainder of the shaft.
[0060] Base plate
[0066] The present disclosure also relates to a base plate. The base plate has an upper portion and a lower portion and includes a BeO composition, such as the second BeO composition described above. Due to its composition and optional processing, the base plate demonstrates the superior performance characteristics disclosed herein. In particular, the base plate demonstrates the clamping pressure described herein.
[0061]
[0067] In some embodiments, the second BeO composition, e.g., the BeO composition of the base plate, comprises a high purity level of BeO. It has been discovered that the purity level of the beryllium oxide composition for the base plate (optionally together with its processing to form the base plate) advantageously contributes to high temperature performance. Also, the BeO utilized in the second BeO composition (or the first BeO composition for that matter) may be processed to achieve a particular purity level. Furthermore, the base plate contains few, e.g., less than 3, less than 2, individual (laminated) layers. In some cases, the base plate does not have individual layers, thereby beneficially eliminating the traditional problems of delamination and degradation.
[0062]
[0068] BeO may be present in an amount ranging from 50 wt% to 99.99 wt%, e.g., from 75 wt% to 99.95 wt%, from 75 wt% to 99.9 wt%, from 85 wt% to 99.7 wt%, from 90 wt% to 99.7 wt%, or from 92 wt% to 99.5 wt%. In terms of lower limits, the first BeO composition may comprise more than 50 wt%, e.g., more than 75 wt%, more than 85 wt%, more than 90 wt%, more than 92 wt%, more than 95 wt%, more than 98 wt%, or more than 99 wt% BeO. In terms of upper limits, the first BeO composition may comprise less than 99.99 wt%, e.g., less than 99.95 wt%, less than 99.90 wt%, less than 99.70 wt%, less than 99.50 wt%, or less than 99.0 wt% BeO. In some embodiments, the BeO concentration of the second BeO composition is higher than the BeO concentration of the first BeO composition, e.g., at least 1%, at least 2%, at least 3%, at least 5%, at least 7%, or at least 10% higher. Stated differently, the base plate BeO composition may have a higher purity than the shaft BeO composition, which is advantageous since intrinsic, dielectric, and thermal properties have been found to be more important for the plate top than the shaft.
[0063]
[0069] Without being bound by theory, it is believed that the synergistic performance characteristics of the base plate (or shaft), such as improved high temperature performance, superior clamping pressure, etc., are at least partially a function of the BeO concentration. It has been discovered that conventional base plates (or shafts), such as those including non-BeO ceramics, such as aluminum nitride, aluminum oxide, silicon dioxide, or graphite, as major components, are unable to achieve such performance. In some embodiments, the second BeO composition includes less than 5 wt%, e.g., less than 3 wt%, less than 1 wt%, less than 0.5 wt%, or less than 0.1 wt% of these non-BeO ceramics. In terms of ranges, the second BeO composition may include 0.01 wt% to 5 wt%, e.g., 0.05 wt% to 3 wt%, 0.05 wt% to 1 wt%, or 0.1 wt% to 1 wt% of the non-BeO ceramics.
[0064]
[0070] The second BeO composition may further include fluorine / fluoride ions, and the fluorine / fluoride ions may be present in the amounts described above for the first BeO composition, although, as noted above, in some cases the first BeO composition includes more fluoride ions and / or fluorine than the second BeO composition.
[0065]
[0071] In some cases, the second BeO composition may further include magnesium oxide, silicon dioxide, and / or magnesium trisilicate. The concentrations of these components, and their effect on the microstructure (see above), have been unexpectedly discovered to result in pedestal base plates that demonstrate low corrosion losses and high bulk resistivity. The low resistivity (optionally in combination with other properties) also results in improved clamping forces (in combination with improved high temperature performance).
[0066]
[0072] In some cases, the second BeO composition further comprises magnesium oxide. For example, the second BeO composition may comprise 1 ppb to 10 wt% ppm of magnesium oxide, e.g., 1 ppm to 5 wt%, 10 ppm to 1 wt%, 100 ppm to 1 wt%, 500 ppm to 8000 ppm, 1000 ppm to 8000 ppm, 3000 ppm to 7000 ppm, or 4000 ppm to 6000 ppm of magnesium oxide. In terms of lower limits, the second BeO composition may comprise more than 1 ppb, e.g., more than 10 ppb, more than 1 ppm, more than 10 ppm, more than 100 ppm, more than 500 ppm, more than 1000 ppm, more than 2000 ppm, more than 3000 ppm, or more than 4000 ppm of magnesium oxide. In terms of upper limits, the first BeO composition may include less than 10 wt. % magnesium oxide, eg, less than 5 wt. %, less than 1 wt. %, less than 8000 ppm, less than 7000 ppm, or less than 6000 ppm.
[0067]
[0073] In some cases, the second BeO composition further comprises silica, alumina, yttria, titania, lithia, lanthanum, or magnesium trisilicate, or mixtures thereof, which may be present in the amounts described for magnesium oxide in the second BeO composition.
[0068]
[0074] In some cases, the second BeO composition further comprises a lower concentration of lithia, e.g., 1 ppb to 1 wt%, e.g., 100 ppb to 0.5 wt%, 1 ppm to 0.1 wt%, 100 ppm to 900 ppm, 200 ppm to 800 ppm, 300 ppm to 700 ppm, or 400 ppm to 600 ppm. In terms of lower limits, the second BeO composition may comprise more than 1 ppb, e.g., more than 100 ppb, more than 1 ppm, more than 100 ppm, more than 200 ppm, more than 300 ppm, or more than 400 ppm of lithia. In terms of upper limits, the first BeO composition may contain less than 10 wt.%, e.g., less than 1 wt.%, less than 0.5 wt.%, less than 0.1 wt.% ppm, less than 900 ppm, less than 800 ppm, less than 700 ppm, or less than 600 ppm lithium.
[0069]
[0075] The second BeO composition may further include other components such as carbon, calcium, cerium, iron, hafnium, molybdenum, selenium, titanium, yttrium, or zirconium, or combinations thereof (including oxides, alloys, composites, or allotropes, or combinations thereof). These components may also be present in the second phase of the second BeO composition (and in the base plate). For example, the second BeO composition may include these components in amounts ranging from 1 ppb to 5 wt%, e.g., 10 ppb to 3 wt%, 100 ppb to 1 wt%, 1 ppm to 1 wt%, 1 ppm to 5000 ppm, 10 ppm to 1000 ppm, 50 ppm to 500 ppm, or 50 ppm to 300 ppm. On the upper end, these components may be present in amounts less than 5 wt%, e.g., less than 3 wt%, less than 1 wt%, less than 5000 ppm, less than 1000 ppm, less than 500 ppm, or less than 300 ppm. On the lower end, these components may be present in amounts greater than 1 ppb, e.g., greater than 10 ppb, greater than 100 ppb, greater than 1 ppm, greater than 10 ppm, or greater than 50 ppm.
[0070]
[0076] In some embodiments, the second BeO composition may further include other components as described above for the first BeO composition. The compositional ranges and limits are also applicable to the second BeO composition.
[0071]
[0077] In some embodiments, the first beryllium oxide composition contains more magnesium oxide and / or magnesium trisilicate and / or other components than the second beryllium oxide composition, the microstructural benefits of which are described above.
[0072] Second Phase
[0078] In some cases, the second phase of the second BeO composition may include non-BeO components. For example, the second phase of the second BeO composition constituting the base plate may include magnesia, silica, alumina, yttria, titania, lithia, lanthana, or magnesium trisilicate, or mixtures thereof. The second BeO composition (and base plates made therefrom) may include the second phase non-BeO components, each of which may be present in an amount ranging from 1 ppb to 500 ppm, e.g., 500 ppb to 500 ppm, 1 ppm to 300 ppm, 1 ppm to 200 ppm, 10 ppm to 200 ppm, 50 ppm to 150 ppm, or 75 ppm to 125 ppm. For the upper limit, the first BeO composition may include non-BeO components of the second phase, each present in an amount less than 500 ppm, e.g., less than 300 ppm, less than 200 ppm, less than 150 ppm, or less than 125 ppm. For the lower limit, the second BeO composition may include non-BeO components, each present in an amount greater than 1 ppb, e.g., greater than 500 ppb, greater than 1 ppm, greater than 10 ppm, greater than 25 ppm, greater than 50 ppm, greater than 75 ppm, or greater than 100 ppm. These weight percentages are based on the total weight of the first BeO composition, e.g., the total weight of the shaft.
[0073] performance
[0079] In addition to clamping pressure, the base plate has been discovered to demonstrate a synergistic combination of performance characteristics. For example, the base plate may demonstrate superior performance in one or more of the following: · Temperature uniformity Bulk resistivity Corrosion losses Dielectric constant
[0080] The values and limits of these performance characteristics are described in detail below.
[0074]
[0081] In some embodiments, the base plate has a consistent coefficient of thermal expansion (CTE) from top to bottom, e.g., the CTE does not vary from top to bottom. For example, the coefficient of thermal expansion may vary by less than 25%, e.g., less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, or less than 1% from top to bottom.
[0075]
[0082] In one embodiment, the pedestal, e.g., base plate, demonstrates a short (if any) cleaning cycle time. During operation, cleaning of the pedestal, wafer substrate, and / or chamber, cleaning / removal of assembly overspray may be required. Traditionally, the pedestal assembly requires a cooling step to bring it to a suitable temperature for cleaning, e.g., at least an hour to 300° C., and a subsequent additional heating step, e.g., at least another hour back to the original temperature. Also, the wafer must be stable through these temperature changes. Because of the composition of the pedestal / base plate of the present disclosure, no cooling (or subsequent reheating) is required, cleaning can be performed at the operating temperature, cleaning cycle times are minimized (if not eliminated), and the wafers do not have to be (as) stable. In some embodiments, the cleaning cycle time of the pedestal / base plate is less than 2 hours, e.g., less than 1.5 hours, less than 1 hour, less than 45 minutes, less than 30 minutes, less than 20 minutes, less than 10 minutes, or less than 5 minutes.
[0076]
[0083] In some cases, the disclosure further relates to a method for cleaning a contaminated pedestal assembly / wafer / chamber. The method includes providing a pedestal assembly and wafer in a chamber (place the wafer on top of the pedestal assembly) and heating the wafer to an operating temperature of at least 400° C., at least 450° C., at least 500° C., at least 550° C., at least 600° C., at least 650° C., or at least 700° C. Once the manufacturing temperature (if contaminated) is reached, the method includes cooling the wafer to a cooling temperature below 150° C., e.g., below 100° C., below 50° C., below 25° C., or below 10° C. (or no cooling at all for BeO) and cleaning the plate at the cooling temperature. In some embodiments, the method further comprises reheating the wafer to an operating temperature of at least 400° C., at least 450° C., at least 500° C., at least 550° C., at least 600° C., at least 650° C., or at least 700° C. Importantly, the cleaning cycle time from cooling to reheating is shorter than conventional methods, e.g., less than 2 hours, e.g., less than 1.5 hours, less than 1 hour, less than 45 minutes, less than 30 minutes, less than 20 minutes, less than 10 minutes, or less than 5 minutes. Beneficially, due to the composition of the pedestal / baseplate of the present disclosure, cooling (or subsequent reheating) is not necessary or is minimized, cleaning can be performed at the operating temperature (or slightly below), cleaning cycle time is minimized (if not eliminated), and the wafer does not have to be (as) stable.
[0077]
[0084] The base plate of the present disclosure may be larger in size than some conventional base plates, yet still demonstrate the superior performance characteristics described herein. Traditionally, manufacturers have struggled to produce large base plates that demonstrate suitable characteristics. As is known in the art, as the size of the base plate increases, it becomes more difficult to manufacture the base plate while maintaining performance. Some of the reasons include the high CTE of conventional pedestal materials, which detrimentally leads to cracking problems, and the size limitations of conventional commercial equipment. In some embodiments, the minimum lateral dimension of the base plate is at least 100 mm, such as at least 125 mm, at least 150 mm, at least 175 mm, at least 200 mm, at least 225 mm, at least 250 mm, at least 300 mm, at least 400 mm, at least 500 mm, at least 750 mm, or at least 1000 mm.
[0078]
[0085] The base plate, in some embodiments, has a flatness with a camber of less than 50 microns, for example, less than 40 microns, less than 30 microns, less than 25 microns, less than 15 microns, less than 10 microns, or less than 5 microns, over a distance of 300 mm.
[0079]
[0086] In some cases, the base plate further includes a mesa (standoff). The mesa is used to lift the wafer. In some embodiments, the mesa protrudes upward from the top surface of the base plate. The mesa may have an average height in the range of 1 micron to 50 microns, e.g., 1.5 microns to 40 microns, 2 microns to 30 microns, 2 microns to 20 microns, 2.5 microns to 18 microns, or 5 microns to 15 microns. In terms of lower limits, the mesa may have an average height greater than 1 micron, e.g., greater than 1.5 microns, greater than 2 microns, greater than 2.5 microns, greater than 3 microns, or greater than 5 microns. In terms of upper limits, the mesa may have an average height less than 50 microns, e.g., less than 40 microns, less than 30 microns, less than 20 microns, less than 18 microns, or less than 15 microns.
[0080]
[0087] In some cases, the base plate further includes a heating element enclosed within the base plate. In some examples, the heating element is a coiled or crimped heating element. The combination of the BeO composition and / or the crimped or coiled heating element surprisingly results in improved temperature uniformity (see below) compared to conventional base plates using non-BeO ceramics and / or other types of heating elements.
[0081]
[0088] The base plate may further include other hardware, such as an antenna. These features are described in more detail below. In some cases, the antenna and / or heating element includes niobium and / or platinum and / or titanium. The inventors have discovered that niobium and / or platinum and / or titanium, when used with BeO compositions, provide a synergistic effect in thermal expansion coefficient, as well as unexpected performance in terms of corrosion resistance and electrical resistance. In some cases, these metals, when used as hardware, have a thermal compatibility factor that synergizes well with BeO materials. The thermal compatibility factor has been found to prevent stress-induced failures due to, for example, temperature cycling.
[0082] Base plate gradient concept / performance
[0089] The present disclosure also relates to base plates designed to have various property gradients from top to bottom. These base plates can be manufactured by forming a precursor utilizing multiple powders, each with different properties, and then heating the precursor to form a base plate with a property gradient. Importantly, the resulting base plate does not include separate layers, benefiting the overall layered base plate assembly.
[0083]
[0090] In some embodiments, the base plate is manufactured from two or more grades of raw BeO powder. In one embodiment, the top surface includes a first grade, the bottom surface includes a second grade, and the middle region includes a mixture of the first and second grades. For example, the first grade may be a higher purity / higher thermal conductivity / higher (theoretical) density / lower porosity material, and the second grade may be a lower purity / lower thermal conductivity / lower (theoretical) density / higher porosity material. Of course, various other numbers and combinations of raw BeO powder are contemplated.
[0084]
[0091] The base plate may demonstrate one or more of the following desirable performance gradients: A decreasing thermal conductivity gradient from top to bottom A decreasing resistivity gradient from top to bottom Purity gradient decreasing from top to bottom Theoretical density gradient decreasing from top to bottom A dielectric constant gradient that increases from top to bottom
[0092] Each of these performance gradients has an "upper value" when measured at the top of the plate and a "lower value" when measured at the bottom of the plate. The endpoints of the ranges herein may be utilized as upper and lower limits. For example, a range of 231-350 W / mK may occur, with an upper limit of less than 350 W / mK and a lower limit of 231 W / mK.
[0085]
[0093] Thermal Conductivity: In some embodiments, the base plate has an upper thermal conductivity in the range of 125-400 W / mK, e.g., 231-350 W / mK, 250-350 W / mK, 265-335 W / mK, or 275-325 W / mK, when measured at room temperature. The base plate can have a lower thermal conductivity in the range of 146-218 W / mK, e.g., 150-215 W / mK, 160-205 W / mK, 165-200 W / mK, or 170-190 W / mK, when measured at room temperature. In terms of upper limits, the base plate may have a thermal conductivity of less than 400 W / mK at room temperature, e.g., less than 375 W / mK, less than 350 W / mK, less than 300 W / mK, less than 275 W / mK, less than 255 W / mK, or less than 250 W / mK.
[0086]
[0094] The base plate can have an upper thermal conductivity in the range of 25 to 105 W / mK, e.g., 35 to 95 W / mK, 45 to 85 W / mK, or 55 to 75 W / mK, when measured at 800° C. The base plate can have a lower thermal conductivity in the range of 1 to 21 W / mK, e.g., 3 to 20 W / mK, 5 to 15 W / mK, 7 to 13 W / mK, or 9 to 11 W / mK, when measured at 800° C.
[0087]
[0095] Generally, the lower thermal conductivity will be lower than the upper thermal conductivity, which may be at least 6%, e.g., at least 10%, at least 20%, at least 35%, at least 50%, at least 100%, or at least 200% higher than the lower thermal conductivity when measured at room temperature or at 800° C., or regardless of the temperature at which it is measured.
[0088]
[0096] Resistivity: In some cases, the upper resistivity is greater than 1×10 at room temperature. 5 ~1×10 16 ohm m, e.g. 1 x 10 6 ~1×10 16 , 1×10 7 ~5×10 15 , 1×10 8 ~1×10 15 , or 1 × 10 9 ~1×10 15The resistivity is in the ohm range. The lower resistivity can be lower than the upper resistivity. The lower resistivity is in the range of 1×10 5 ~1×10 16 ohm m, e.g. 1 x 10 5 ~1×10 15 , 1×10 5 ~5×10 14 , 1×10 6 ~1×10 13 , or 1 × 10 7 ~5×10 12 It may be in the ohm range.
[0089]
[0097] In these cases, the top resistivity is higher than the bottom resistivity. Typically, the bottom resistivity will be at least 150%, at least 200%, at least 250%, at least 300%, at least 500%, or at least 1000% lower than the top resistivity.
[0090]
[0098] Purity: The upper purity level, in some embodiments, is in the range of 99.0% to 99.9%, e.g., 99.1% to 99.9%, 99.4% to 99.8%. The lower purity level may be in the range of 95.0% to 99.5%, e.g., 95.5% to 99.5%, 96% to 99%, or 96.5% to 98.5%. Typically, the lower purity level will be at least 0.2%, at least 0.4%, at least 0.5%, or at least 1.0% lower than the upper purity level.
[0091]
[0099] Theoretical density: In some cases, the upper theoretical density may be in the range of 93-200, e.g., 94-100, 95-100, 96-99.5, or 97-99. The lower theoretical density may be in the range of 93-100, e.g., 94-99.5, 95-99, or 96-98. In general, the lower theoretical density will be lower than the upper theoretical density. The upper theoretical density may be at least 0.1%, e.g., at least 0.2%, at least 0.4%, at least 0.5%, or at least 1.0%, higher than the lower theoretical density.
[0092]
[0100] The theoretical density of the base plate may be similar to the theoretical density of the shaft. In some cases, the theoretical density of the shaft is lower than the theoretical density of the base plate and / or the porosity of the shaft is higher than the porosity of the base plate.
[0093]
[0101] Particle size: In some cases, the upper (maximum) particle size may be in the range of 5 to 60 microns, e.g., 10 to 50 microns, 15 to 45 microns, or 20 to 40 microns. The lower (maximum) particle size may be in the range of 10 to 100 microns, e.g., 20 to 90 microns, 25 to 85 microns, or 30 to 80 microns. Generally, the lower (maximum) particle size will be larger than the upper particle size. The upper particle size may be at least 0.1%, e.g., at least 0.2%, at least 0.4%, at least 0.5%, or at least 1.0% smaller than the lower particle size.
[0094]
[0102] Grain Boundaries: In some cases, the overall grain boundaries may range from amorphous to 10 microns, e.g., 1-9 microns, 2-8 microns, or 3-7 microns. In some cases, the lower grain boundaries will be smaller than the upper grain boundaries. In other embodiments, the upper grain boundaries will be smaller than the lower grain boundaries.
[0095]
[0103] Specific heat: In some embodiments, the base plate has an upper specific heat in the range of 0.9 to 1.19 J / gK, e.g., 0.95 to 1.15 J / gK, or 1.0 to 1.1 J / gK, when measured at room temperature. The base plate may have a lower specific heat in the range of 0.9 to 1.19 J / gK, e.g., 0.95 to 1.15 J / gK, or 1.0 to 1.1 J / gK, when measured at room temperature.
[0096]
[0104] The base plate may have an upper specific heat in the range of 1.8 to 2.06 J / gK, e.g., 1.85 to 2.03 J / gK, or 1.87 to 1.97 J / gK, when measured at 800° C. The base plate may have a lower specific heat in the range of 1.8 to 2.03 J / gK, e.g., 1.85 to 2.03 J / gK, or 1.87 to 1.97 J / gK, when measured at 800° C.
[0097]
[0105] Generally, the lower specific heat will be lower than the upper specific heat, which may be at least 0.5%, e.g., at least 1%, at least 2%, at least 5%, at least 10%, or at least 20% higher than the lower specific heat when measured at room temperature or at 800° C., or regardless of the temperature measured.
[0098]
[0106] Thermal diffusivity: In some embodiments, the base plate has a thermal diffusivity of 90 to 115 mm when measured at room temperature. 2 / sec, e.g., 95~110mm 2 / sec, or 97~108mm 2 The base plate has a top thermal diffusivity in the range of 58 to 115 mm / sec when measured at room temperature. 2 / sec, e.g., 65~105mm 2 / sec, or 75~95mm 2 1 / sec.
[0099]
[0107] The base plate is 5 to 21 mm when measured at 800°C. 2 / sec, e.g., 7~19mm 2 / sec, 9~17mm 2 / sec, or 10-15mm 2 The base plate may have a top thermal diffusivity in the range of 3 to 7.7 mm / sec when measured at 800° C. 2 / sec, e.g., 3.5 to 7 mm 2 / sec, or 4 to 6 mm 2 1 / sec.
[0100]
[0108] Generally, the lower thermal diffusivity will be lower than the upper thermal diffusivity, which may be at least 0.5%, e.g., at least 1%, at least 2%, at least 5%, at least 10%, or at least 20% higher than the lower thermal diffusivity when measured at room temperature or at 800° C., or regardless of the temperature measured.
[0101]
[0109] Permeability: In some embodiments, the base plate has a permeability of 22.0 to 30.02 S when measured at room temperature. 0.5 W / K / km 2 For example, 24.0~30.02S 0.5 W / K / km 2 , 25.0~29.0S 0.5 W / K / km 2 , or 26.0~28.0S 0.5 W / K / km 2 The base plate has an upper permeability in the range of 1.0 to 25.0 S when measured at room temperature. 0.5 W / K / km 2 , for example, 3.0~24.0S 0.5 W / K / km 2 , or 5.0~23.0S 0.5 W / K / km 2 In some embodiments, the base plate may have a lower thermal effusivity in the range of 22.0 S. 0.5 W / K / km 2 Ultra, for example, 23.0S 0.5 W / K / km 2 Ultra, 24.0S 0.5 W / K / km 2 Ultra, 25.0S 0.5 W / K / km 2 Ultra, 27.0S 0.5 W / K / km 2 Ultra, 28.0S 0.5 W / K / km 2 Over or 30.0S 0.5 W / K / km 2 It has an ultra (upper) permeability.
[0102]
[0110] The base plate is 11.0 to 16.4 S when measured at 800 °C. 0.5 W / K / km2 For example, 12.0 to 15.0 S 0.5 W / K / km 2 , 12.5~14.5S 0.5 W / K / km 2 , or 13.0~14.0S 0.5 W / K / km 2 The base plate may have an upper permeability in the range of 0.1 to 12.0 S when measured at 800°C. 0.5 W / K / km 2 , e.g., 0.5~11.0S 0.5 W / K / km 2 , or 1.0~10.0S 0.5 W / K / km 2 In some embodiments, the base plate may have a lower thermal effusivity in the range of 14.0 S. 0.5 W / K / km 2 Ultra, for example, 15.0S 0.5 W / K / km 2 Ultra, 16.0S 0.5 W / K / km 2 Ultra, 17.0S 0.5 W / K / km 2 Ultra, 18.0S 0.5 W / K / km 2 Ultra, 19.0S 0.5 W / K / km 2 Ultra or 20.0S 0.5 W / K / km 2 The improved permeability may also be demonstrated at other temperatures, for example as shown in the examples.
[0103]
[0111] Generally, the bottom permeability will be lower than the top permeability, which may be at least 0.5%, e.g., at least 1%, at least 2%, at least 5%, at least 10%, or at least 20% higher than the bottom permeability when measured at room temperature or at 800° C., or regardless of the temperature at which it is measured.
[0104]
[0112] Average CTE: In some embodiments, the base plate has a top average CTE in the range of 7.0-9.5, e.g., 7.2-9.3, 7.5-9.0, or 7.7-8.8. The base plate may have a bottom average CTE in the range of 7.0-9.5, e.g., 7.2-9.3, 7.5-9.0, or 7.7-8.8. In some cases, the bottom average CTE will be lower than the top average CTE. In other cases, the bottom average CTE will be higher than the top average CTE. The difference may be at least 0.5%, e.g., at least 1%, at least 2%, at least 5%, at least 10%, or at least 20%, when measured at room temperature or at 800° C., or regardless of the temperature measured.
[0105]
[0113] In some embodiments, the upper dielectric constant ranges from 1 to 20, e.g., from 15, 3 to 12, or 5 to 9. The lower dielectric constant may be similar to the upper dielectric constant. In some cases, the lower dielectric constant may be higher than the upper dielectric constant. In other cases, the upper dielectric constant may be higher than the lower dielectric constant.
[0106]
[0114] Base plates having desired performance gradients may be formed for the BeO compositions described herein, and in some cases modified in composition parameters to achieve the gradients, and may also demonstrate other performance characteristics, such as clamping pressure, corrosion loss, temperature uniformity, etc., as disclosed herein.
[0107] Shaft gradient concept / performance
[0115] In some embodiments, the shaft has an upper thermal conductivity in the range of 146 W / mK to 218 W / mK, e.g., 150 W / mK to 215 W / mK, 160 W / mK to 205 W / mK, 165 W / mK to 200 W / mK, or 170 W / mK to 190 W / mK, when measured at room temperature. The shaft may have a lower thermal conductivity in the range of 1 W / mK to 218 W / mK, e.g., 50 W / mK to 218 W / mK, 100 W / mK to 218 W / mK, 146 W / mK to 218 W / mK, 150 W / mK to 215 W / mK, 160 W / mK to 205 W / mK, 165 W / mK to 200 W / mK, or 170 W / mK to 190 W / mK, when measured at room temperature.
[0108]
[0116] The shaft may have an upper thermal conductivity in the range of 1 to 21, e.g., 3 to 20, 5 to 15, 7 to 13, or 9 to 11, when measured at 800° C. The shaft may have a lower thermal conductivity in the range of 1 to 21, e.g., 3 to 20, 5 to 15, 7 to 13, or 9 to 11, when measured at 800° C.
[0109]
[0117] Generally, the lower thermal conductivity will be lower than the upper thermal conductivity. The upper thermal conductivity may be at least 6% higher than the lower thermal conductivity when measured at room temperature or at 800° C., or regardless of the measured temperature, e.g., at least 10%, at least 20%, at least 35%, at least 50%, at least 100%, or at least 200% higher. In some cases, the slope may be nonlinear, e.g., a stepwise function or a maximum integer function. In other cases, the slope may be linear.
[0110] General performance
[0118] The base plate and shaft also demonstrate excellent performance figures, generally without gradient consideration. In some cases, the performance areas and limits of the base plate may be similar, generally or in whole, to the "upper values" and / or "lower values" above. These will not be repeated for brevity. Additional performance areas and limits are also provided.
[0111]
[0119] Thermal diffusivity: In some embodiments, the base plate has a thermal diffusivity of 75 to 115 mm when measured at room temperature. 2 / sec, e.g., 90~115mm 2 / sec, 95~110mm 2 / sec, or 97~108mm 2 The base plate has a (top) thermal diffusivity in the range of 58 to 115 mm / sec when measured at room temperature. 2 / sec, e.g., 65~105mm 2 / sec, or 75~95mm 2 In some embodiments, the base plate may have a lower thermal diffusivity in the range of 75 mm / sec. 2 / sec or more, e.g., 80mm 2 > / sec, 85mm 2 > / sec, 90mm 2 > / sec, 95mm 2 > / sec, 100mm 2 / sec or 110mm 2 / sec (upper) thermal diffusivity.
[0112]
[0120] The base plate is 5 to 21 mm when measured at 800°C. 2 / sec, e.g., 7~19mm 2 / sec, 9~17mm 2 / sec, or 10-15mm 2 The base plate may have a top thermal diffusivity in the range of 3 to 7.7 mm / sec when measured at 800° C. 2 / sec, e.g., 3.5 to 7 mm 2 / sec, or 4 to 6 mm 2 In some embodiments, the base plate may have a lower thermal diffusivity in the range of 5 mm / sec. 2 / sec or more, e.g., 10 mm 2 > / sec, 12mm 2 > / sec, 14mm 2 > / sec, 15mm 2 / sec or more than 20mm 2 / sec (upper) The improved thermal diffusivity may also be demonstrated at other temperatures, for example as shown in the examples.
[0113]
[0121] Specific Heat: In some embodiments, the base plate has an upper specific heat in the range of 0.7-1.19 J / gK, e.g., 0.9-1.19 J / gK, 0.95-1.15 J / gK, or 1.0-1.1 J / gK, when measured at room temperature. The base plate may have a lower specific heat in the range of 0.9-1.19 J / gK, e.g., 0.95-1.15 J / gK, or 1.0-1.1 J / gK, when measured at room temperature. In some embodiments, the base plate has an (upper) specific heat of greater than 0.7 J / gK, e.g., greater than 0.8 J / gK, greater than 0.9 J / gK, greater than 0.95 J / gK, or greater than 1.0 J / gK.
[0114]
[0122] The base plate may have an upper specific heat in the range of 1.0-2.06 J / gK, e.g., 1.8-2.06 J / gK, 1.85-2.03 J / gK, or 1.87-1.97 J / gK, when measured at 800°C. The base plate may have a lower specific heat in the range of 1.8-2.03 J / gK, e.g., 1.85-2.03 J / gK, or 1.87-1.97 J / gK, when measured at 800°C. In some embodiments, the base plate has an (upper) specific heat of greater than 1.0 J / gK, e.g., greater than 1.5 J / gK, greater than 1.7 J / gK, greater than 1.8 J / gK, or greater than 1.85 J / gK. Specific heat improvement may also be demonstrated at other temperatures, e.g., as shown in the Examples.
[0115]
[0123] Thermal Conductivity: In one embodiment, the second beryllium oxide composition (and base plate) generally has a thermal conductivity at room temperature of less than 400 W / mK, e.g., less than 375 W / mK, less than 350 W / mK, less than 300 W / mK, less than 275 W / mK, less than 255 W / mK, or less than 250 W / mK. In terms of range, the second beryllium oxide composition has a thermal conductivity in the range of 125 W / mK to 400 W / mK, e.g., 145 W / mK to 350 W / mK, 175 W / mK to 325 W / mK, or 200 W / mK to 300 W / mK. In some embodiments, the base plate has a (top) thermal conductivity of greater than 125 W / mK, e.g., greater than 150 W / mK, greater than 175 W / mK, greater than 200 W / mK, greater than 250 W / mK, or greater than 255 W / mK. The thermal conductivity can be measured at the top of the base plate.
[0116]
[0124] In one embodiment, the second beryllium oxide composition (and base plate) generally has a thermal conductivity of less than 150 W / mK at 800° C., e.g., less than 105 W / mK, less than 95 W / mK, less than 85 W / mK, or less than 75 W / mK. In terms of ranges, the second beryllium oxide composition has a thermal conductivity in the range of 25-105 W / mK, e.g., 35-95 W / mK, 45-85 W / mK, or 55-75 W / mK, when measured at 800° C. The thermal conductivity can be measured at the top of the base plate. In some embodiments, the base plate has a (top) thermal conductivity of greater than 25 W / mK, e.g., greater than 30 W / mK, greater than 35 W / mK, greater than 40 W / mK, greater than 42 W / mK, or greater than 45 W / mK. The improved thermal conductivity can also be shown at other temperatures, e.g., as shown in the examples. The thermal conductivity can be measured at the top of the base plate.
[0117]
[0125] Thermal Conductivity of the Shaft: In some embodiments, the first beryllium oxide composition (and shaft) generally has a thermal conductivity at room temperature of less than 300 W / mK, e.g., less than 275 W / mK, less than 250 W / mK, less than 225 W / mK, less than 220 W / mK, less than 218 W / mK, or less than 210 W / mK. In terms of ranges, the first beryllium oxide composition has a thermal conductivity in the range of 100 W / mK to 300 W / mK, e.g., 125 W / mK to 275 W / mK, 125 W / mK to 250 W / mK, or 140 W / mK to 220 W / mK. In some embodiments, the shaft has a (top) thermal conductivity of greater than 125 W / mK, e.g., greater than 150 W / mK, greater than 175 W / mK, greater than 200 W / mK, greater than 250 W / mK, or greater than 255 W / mK. The thermal conductivity can be measured at the top of the base plate. The thermal conductivity can be measured at the top of the shaft.
[0118]
[0126] In some cases, the first beryllium oxide composition (and base plate) generally has a thermal conductivity of less than 25 W / mK at 800° C., e.g., less than 23 W / mK, less than 21 W / mK, less than 20 W / mK, less than 15 W / mK, less than 10 W / mK, or less than 5 W / mK. In terms of ranges, the second beryllium oxide composition has a thermal conductivity in the range of 1-5 W / mK, e.g., 2-23 W / mK, 4-21 W / mK, or 5-20 W / mK, when measured at 800° C. In some embodiments, the shaft has a (top) thermal conductivity of greater than 25 W / mK, e.g., greater than 30 W / mK, greater than 35 W / mK, greater than 40 W / mK, greater than 42 W / mK, or greater than 45 W / mK. Improved thermal conductivity may also be demonstrated at other temperatures, e.g., as shown in the examples. The thermal conductivity can be measured at the top of the base plate.
[0119]
[0127] Theoretical Density of the Shaft: In some embodiments, the first BeO composition (and shaft) generally has a theoretical density in the range of 90-100, e.g., 92-100, 93-99, 95-99, or 97-99. On the lower end, the shaft has a theoretical density greater than 90, e.g., greater than 92, greater than 93, greater than 95, or greater than 97. On the upper end, the shaft has a theoretical density less than 100, e.g., less than 99.5, less than 99, less than 98.7, or less than 98. It is contemplated that the desired theoretical density and porosity may result from the microstructural features, e.g., grain boundaries and grain size, provided by the first BeO composition.
[0120]
[0128] In some embodiments, the base plate is heated to 1×10 4 Ohm m, e.g., 5 x 10 4 Super, 1×10 5 Super, 5×10 5 Super, 1×10 6 Super, 5×10 6 Super, 1×10 7 Super, 5×10 7 Super, 1×10 8 Super, 5×10 8 Super, 1×10 9 Super, or 1×10 10 The present invention demonstrates a bulk resistivity of greater than 100 nm, which advantageously results, at least in part, in improved clamping performance.
[0121]
[0129] The inventors have discovered that it may be beneficial for the shaft to be of lower density / higher porosity than the base plate, and the microstructure of each BeO composition is tailored accordingly, as disclosed herein. Such a configuration is believed to surprisingly avoid the heat sink effect (creation of cold spots) and / or avoid deformation (melting) of the original plate / shaft seal.
[0122]
[0130] The theoretical density of the pedestal component is an important characteristic. In some cases, the theoretical density (and / or porosity) affects or contributes to thermal conductivity.
[0131] It has been found that porosity beneficially inhibits the spread of microfractures. In some embodiments, the base plate and / or shaft has a porosity in the range of 0.1% to 10%, e.g., 0.5% to 8%, 1% to 7%, 1% to 5%, or 2% to 4%. In terms of the upper limit, the base plate and / or shaft may have a porosity of less than 10%, e.g., less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or less than 1%. In terms of the lower limit, the base plate and / or shaft may have a porosity of more than 1%, e.g., more than 2%, more than 3%, more than 4%, more than 5%, more than 6%, more than 7%, more than 8%, or more than 9%.
[0123]
[0132] The second BeO composition advantageously contributes to uniform temperature performance across the base plate, especially at high temperatures. Such temperature uniformity has not been achieved using conventional non-BeO ceramics. In some embodiments, the base plate demonstrates temperature variations of less than ±3%, e.g., less than ±2.5%, less than ±2%, less than ±1%, or less than ±0.5%, when heated to temperatures above 700° C., e.g., above 750° C., above 800° C., or above 850° C. Temperature can be measured, for example, via a thermocouple, IR, or TCR device on the top surface of the plate, as known in the art.
[0124]
[0133] The base plate may in some cases demonstrate a corrosion loss of less than 0.016 wt%, e.g., less than 0.015 wt%, less than 0.013 wt%, less than 0.012 wt%, less than 0.010 wt%, less than 0.008 wt%, or less than 0.005 wt% after 200 cycles. Corrosion loss may be checked by weighing the sample before and after cycling it according to the test protocol (e.g., 200 cycles (5.5 hours) in NF3 at 400° C. and 4 cycles (12 hours) in ClF at 300° C.).
[0125]
[0134] The base plate may in some cases demonstrate a change in decomposition of less than 1 wt%, e.g., less than 0.1 wt%, or less than 0.005 wt%, at temperatures above 1600°C. Decomposition may be defined as the decomposition (or, in some cases, dissociation), e.g., chemical change, into its precursor components. The base plate of the present disclosure has been found to advantageously have improved softening and decomposition points. In some embodiments, the base plate has a softening point of greater than 1600°C, e.g., greater than 1700°C, greater than 1750°C, greater than 1800°C, greater than 1850°C, greater than 1900°C, or greater than 2000°C. In some embodiments, the base plate has a melting point (in nitrogen gas) of greater than 2200°C, e.g., greater than 2325°C, greater than 2350°C, greater than 2400°C, greater than 2450°C. Unlike conventional base plates, the base plate of the present disclosure is capable of applying the aforementioned clamping pressures at these temperatures. Conventional base plates, for example aluminum nitride base plates, decompose at temperatures below 1600°C and melt at temperatures below 2200°C.
[0126]
[0135] In some embodiments, the base plate has a dielectric constant less than 20, eg, less than 17, less than 15, less than 12, less than 10, less than 8, or less than 7.
[0136] In some examples, the base plate has a surface hardness of at least 50 Rockwell, e.g., at least 50 Rockwell, at least 52 Rockwell, at least 55 Rockwell, at least 57 Rockwell, at least 60 Rockwell, at least 65 Rockwell, or at least 70 Rockwell, when measured on a 45N scale.
[0127]
[0137] In some embodiments, the base plate has a coefficient of thermal expansion ranging from 5 to 15, e.g., 6 to 13, 6.5 to 12, 7 to 9.5, 7.5 to 9, or 7 to 9 across the base plate. On the lower end, the base plate may have a coefficient of thermal expansion greater than 5, e.g., greater than 6, greater than 6.5, greater than 7, or greater than 7.5. On the upper end, the base plate may have a coefficient of thermal expansion less than 15, e.g., less than 13, less than 12, less than 9.5, or less than 9. The coefficient of thermal expansion varies by less than 25% from top to bottom, e.g., less than 10%, less than 5%, less than 3%, or less than 1%.
[0128] Pedestal Assembly Combination
[0138] The base plate and shaft of the present disclosure may be used in conjunction with one another. Alternatively, these components may be used in combination with other components known in the art. For example, the base plate of the present disclosure may be used with a conventional shaft, or the shaft of the present disclosure may be used with a conventional base plate.
[0129]
[0139] In some embodiments, the pedestal assembly includes a shaft and a base plate of the present disclosure that includes two or more (laminated) layers and / or co-fired ceramic materials. The layers may be bonded together with a brazing material. Examples of such base plates are those disclosed in U.S. Patent Nos. 7,667,944 and 5,737,178, which are incorporated herein by reference. In addition to the shaft and base plate, these assemblies may further include additional hardware, such as heating elements, antennas, etc.
[0130]
[0140] The present disclosure also relates to a method for producing a base plate. The base plate can be produced from two or more grades of raw BeO powder. BeO powder can be used to form a precursor plate, which is then fired to obtain the base plate. In one embodiment, the top surface includes a first grade, the bottom portion includes a second grade, and the middle region includes a mixture of the first and second grades. Of course, various other numbers and combinations of raw BeO powder are contemplated.
[0131]
[0141] In one embodiment, the method includes providing a first BeO powder and a third BeO powder, and forming a second powder from the first and third powders. The first and second powders may include different grades of raw BeO. The method may further include forming a first (lower) region from the first powder, forming a second (middle) region from the second powder, and forming a third (upper) region from the third powder to form a base plate precursor. The forming step may be accomplished by dispensing each powder into a mold in a predetermined order. The second region may be disposed between the first and third regions. Additional regions formed from additional powders may also be formed in various configurations. The method may further include firing the base plate precursor to form a base plate.
[0132]
[0142] Importantly, in some cases, once the precursor is formed, it may be mixed, e.g., vibrated (optionally under controlled conditions) to partially mix or bond the powder, which can result in a composition gradient after firing. Partial mixing is important to maintain the composition gradient. In some cases, insufficient mixing or complete lack of mixing can result in a completely layered base plate that does not achieve all the benefits described herein. Excessive mixing can result in a homogenous mixture of BeO powder without any of the desired composition gradient.
[0133]
[0143] The method may further include placing a heating element in at least one region and / or crimping the ends. The method further includes cold forming and then firing (sintering) the base plate precursor to form a base plate.
[0134]
[0144] The shaft can be made using a similar method.
[0145] Some embodiments relate to a method of manufacturing a pedestal assembly, the method including providing a base plate of the present disclosure and a shaft of the present disclosure, and connecting the shaft and the base plate. EXAMPLES
[0135] Examples 1 to 4 and Comparative Examples A to C
[0146] Examples 1-4 utilized coupons prepared from different BeO grades, and Comparative Examples A-C utilized coupons prepared from different AlN grades, as shown in Table 1. The coupons were machined from large ceramic block pieces using a standard abrasive diamond grinding and cleaning operation.
[0136] [Table 1]
[0137]
[0147] The coupon dimensions conformed to various ASTM standards, as shown in Table 2.
[0138] [Table 2]
[0139]
[0148] Examples 1-4 and Comparative Examples A-C were tested for thermal diffusivity. Thermal diffusivity was measured using a NETZSCH LFA467HT Hyperflash according to ASTM E1461-13 (2013). Half rise times were greater than 10 ms. Specimens were sputter coated with 0.2 μm gold and spray coated with 5 μm graphite. Specific heat was measured using a Netzsch DSC 404 F1 Pegasus differential scanning calorimeter according to ASTM E1269 (2013). Values at 25° C. are extrapolated.
[0140]
[0149] The thermal diffusivity results are shown in Figure 1. As shown in Figure 1, the BeO of Examples 1-4 beneficially demonstrated significantly higher thermal diffusivities than the AlN Comparative Examples A-C at temperatures up to 500°C. At temperatures above 500°C, Examples 1-4 also exhibited higher thermal diffusivities. While the differences were not large, they were still significant and even small differences contribute to noticeable performance improvements.
[0141]
[0150] Examples 1-4 and Comparative Examples A-C were tested for specific heat. Specific heat is the amount of energy required to change the temperature of a body. The specific heat results are shown in FIG. 2. As shown in FIG. 2, the BeO of Examples 1-4 beneficially exhibited higher specific heat values than the AlN Comparative Examples A-C. In fact, all Examples 1-4 exhibit higher results than all Comparative Examples A-C across the entire temperature range. Advantageously, Examples 1-4 responded more slowly to power fluctuations (lower hysteresis), especially once operating temperatures were reached.
[0142]
[0151] Examples 1-4 and Comparative Examples A-C were tested for thermal conductivity and the results are shown in FIG. 3. Fourier's heat equation was applied to calculate thermal conductivity from the specific heat and thermal diffusivity and density. Thermal conductivity determines the steady state thermal fluctuations of a body. As shown, the BeO of Examples 1-4 advantageously reaches steady state temperature faster than the AlN Comparative Examples A-C at temperatures up to 500° C. At temperatures above 500° C., Examples 1-4 also showed higher thermal conductivity. The difference was not large, but still significant. And as with thermal diffusivity, even a small difference contributes to a noticeable performance improvement.
[0143]
[0152] Examples 1-4 and Comparative Examples A-C were measured for permeability and the results are shown in FIG. 4. The permeability was calculated from the other heat values. The permeability controls the temperature at the moment of contact and junction of the two enclosures, for example, between the heating element and the BeO, and between the BeO and the backside He gas and the Si wafer. As shown, the BeO of Examples 1-4 advantageously exhibits higher permeability values over the entire temperature range than the AlN Comparative Examples A-C. All Examples 1-4 exhibit higher permeability values over the entire temperature range than all Comparative Examples A-C. Examples 1-4 remained at a more stable temperature with less temperature drop and lower thermal stress history when in contact with the backside gas and wafer compared to Comparative Examples A-C.
[0144]
[0153] Examples 1-4 and Comparative Examples A-C were measured for bulk resistivity and the results are shown in FIG. 5. Bulk resistivity was measured using a Keithley 237HV source according to Procedure A of ASTM D257 / ASTM D1829. Bulk resistivity is related to clamping (at elevated temperatures). Higher bulk resistivity at elevated temperatures is beneficial. JR clamping is generally performed at temperatures below 1×10 7 ~1×10 9 Electrostatically active in the range of Ω-m (at 400V to 600V). Figure 5 shows the resistivity gradient of the maximum values for Examples 1 to 4 and Comparative Examples A to C. The gradient of the curves is 1×10 7 ~1×10 9This is related to time in the "chucking / clamping zone" in Ω-m. As shown in Figure 5, Examples 1-4 surprisingly have fairly flat curves and spend more time in the chucking / clamping zone. This demonstrates the improved clamping performance and results in the superior clamping pressure performance disclosed herein, e.g., clamping pressures of at least 133 kPa.
[0145] Examples 5 and 6 Additional samples of BeO material were tested for bulk resistivity in a similar manner. The composition of the BeO material is shown in Table 3. Examples 5 and 6 are prepared from substantially similar mixtures of ceramic powders. Examples 5 and 6 were measured at different facilities and at different times. As shown in Figure 6, the curves for Examples 1, 5 and 6 are very similar and within the typical batch-to-batch variation expected, especially in the chucking / clamping region.
[0146] [Table 3]
[0147]
[0154] The results are shown in Figure 6. As can be seen, Examples 1, 5 and 6 perform particularly well, especially at elevated temperatures.
[0148] Example 7 and Comparative Example D
[0155] Example 7 utilized a coupon containing a BeO composition including BeO (>99.5% purity). Comparative Example D utilized a coupon containing an AlN composition. Example 7 and Comparative Example D were tested for corrosion resistance by measuring the initial weight, processing, and then measuring the final weight. Processing was 200 cycles (5.5 hours) in NF3 at 400° C. and 4 cycles (12 hours) in ClF at 300° C. Example 7 surprisingly demonstrated an average percent loss of only 0.007 wt %, while Comparative Example D demonstrated an average percent loss of 0.016, more than double that of Example 7 (the weight loss of Example 7 was 56% less than that of Comparative Example D).
[0149] Example 8
[0156] The base plate of Example 8 was prepared as follows: A ready to press (RTP) powder was prepared containing a high thermal conductivity grade of BeO and optional binders, lubricants, and sintering aids (high TC powder). A similar powder was prepared using a low thermal conductivity grade of BeO (low TC powder). Predetermined amounts of high and low TC powders were blended to produce an intermediate TC powder.
[0150]
[0157] A platen shaped elastomer / graphite mold was filled with the high TC powder in the bottom third of the volume. A niobium metal heating element in the form of a foil or coating or film or wire was placed in the powder bed. The medium TC powder was then added to the middle third of the volume. A metal ground plane or a radio frequency antenna or a niobium electrode was placed in the powder bed. The top third of the volume was then filled with the low TC powder.
[0151]
[0158] Electrical connection posts and terminals were inserted through the entire powder bed and connected to the metal elements embedded therein. The mold was sealed and pressed at room temperature to compact / densify the powder. The compacted powder shape was bound by an organic or inorganic temporary binder and compacted into a near-net shape object. The object was then sintered in a furnace to induce densification. The object was machined to the finished dimensional requirements, thus resulting in the final base plate with various property gradients disclosed herein. Forces and / or other connections were applied to the electrical connection posts to operate the device for heating and electrostatic chucking.
[0152]
[0159] The base plate was heated in a test chamber such that the surface of a silicon wafer mounted on the base plate reached a temperature of 800° C. (the temperature at which semiconductor fabrication chambers are preferably operated). Surprisingly, the base plate performed very well at the high temperatures. For example, the base plate did not crack and demonstrated bulk resistivity performance, e.g., resistivity, similar to the values shown above (FIG. 5). These unexpected resistivity values correlate with excellent clamping performance (e.g., electrostatic chucking / clamping is maintained (at high temperatures)) at high temperatures. Such performance has not been achieved with conventional base plate materials, e.g., AlN.
[0153] Embodiment
[0160] Among other things, the following embodiments are disclosed:
[0161] Embodiment 1: A pedestal assembly comprising a shaft containing a first beryllium oxide composition containing beryllium oxide and fluorine / fluoride ions, and a base plate containing a second beryllium oxide composition containing at least 95 wt% beryllium oxide and optional fluorine / fluoride ions, wherein the base plate demonstrates a clamping pressure of at least 133 kPa.
[0154]
[0162] Embodiment 2: The embodiment of embodiment 1, wherein the first beryllium oxide composition comprises from 1 ppb to 1000 ppm of fluorine / fluoride ions.
[0163] Embodiment 3: The embodiment of embodiment 1 or 2, wherein the first beryllium oxide composition comprises more fluorine / fluoride ions than the second beryllium oxide composition.
[0155]
[0164] Embodiment 4: Any of embodiments 1-3, wherein the first beryllium oxide composition is treated to achieve a fluorine / fluoride ion concentration.
[0165] Embodiment 5: Any of embodiments 1-4, wherein the first beryllium oxide composition further comprises less than 50 wt.% magnesium oxide and less than 50 wt.% ppm silicon dioxide.
[0156]
[0166] Embodiment 6: Any of the embodiments 1-5, wherein the first beryllium oxide composition further comprises 1 ppb to 50 wt% ppm of alumina, 1 ppb to 10,000 ppm of sulfite, and / or 1 ppb to 1 wt% ppm of boron, barium, sulfur, or lithium, or a combination thereof (including an oxide, alloy, complex, or allotrope, or a combination thereof).
[0157]
[0167] Embodiment 7: Any of embodiments 1-6, wherein the first beryllium oxide composition has an average grain boundary greater than 0.1 microns.
[0168] Embodiment 8: Any of embodiments 1-7, wherein the first beryllium oxide composition has an average particle size of less than 100 microns.
[0158]
[0169] Embodiment 9: The embodiment of any of embodiments 1-8, wherein the second beryllium oxide composition comprises 1 ppb to 10 wt% ppm of magnesium oxide and 1 ppb to 10 wt% ppm of silicon dioxide.
[0159]
[0170] Embodiment 10: Any of embodiments 1-9, wherein the second beryllium oxide composition comprises 1 ppb to 10 wt% ppm magnesium trisilicate.
[0171] Embodiment 11: Any of embodiments 1-10, wherein the first beryllium oxide composition comprises more magnesium oxide and / or magnesium trisilicate than the second beryllium oxide composition.
[0160]
[0172] Embodiment 12: The embodiment of any of embodiments 1-11, wherein the second beryllium oxide composition comprises from 1 ppb to 1 wt % lithia.
[0173] Embodiment 13: Any of embodiments 1-12, wherein the first beryllium oxide composition comprises less than 75 wt.% aluminum nitride and / or the second beryllium oxide composition comprises less than 5 wt.% aluminum nitride.
[0161]
[0174] Embodiment 14: Any of embodiments 1-13, wherein the first beryllium oxide composition has a conductivity of less than 300 W / mK at room temperature.
[0175] Embodiment 15: Any of embodiments 1-14, wherein the second beryllium oxide composition has a conductivity of less than 400 W / mK at room temperature.
[0162]
[0176] Embodiment 16: The embodiment of any of embodiments 1-15, wherein the first beryllium oxide composition has a theoretical density in the range of 90% to 100%.
[0177] Embodiment 17: Any of embodiments 1-16, wherein the base plate demonstrates a temperature variation of less than ±3% when heated to a temperature above 700° C.
[0163]
[0178] Embodiment 18: The base plate is 1×10 4 Any of the embodiments of embodiments 1-17, demonstrating a bulk resistivity of greater than ohm m.
[0179] Embodiment 19: Any of embodiments 1-18, wherein the base plate demonstrates a corrosion loss of less than 0.016 wt%.
[0164]
[0180] Embodiment 20: Any of embodiments 1-19, wherein the base plate has a dielectric constant of less than 20.
[0181] Embodiment 21: Any of embodiments 1-20, wherein the base plate has a surface hardness of at least 50 Rockwell on a 45N scale.
[0165]
[0182] Embodiment 22: Any of the embodiments of embodiments 1-21, wherein the base plate has a coefficient of thermal expansion in the range of 5 to 15 throughout the base plate.
[0183] Embodiment 23: The embodiment of any of embodiments 1-22, further comprising a heating element enclosed in the base plate.
[0166]
[0184] Embodiment 24: Any of embodiments 1 to 23, wherein the smallest lateral dimension across the base plate is at least 100 mm.
[0185] Embodiment 25: Any of embodiments 1-24, wherein the base plate has a camber flatness of less than 50 microns over a distance of 300 mm.
[0167]
[0186] Embodiment 26: Any of embodiments 1-25, wherein the base plate optionally further comprises a mesa having a height greater than 1 micron.
[0187] Embodiment 27: Any of embodiments 1-26, wherein the shaft includes a stub portion having a similar coefficient of thermal expansion.
[0168]
[0188] Embodiment 28: Any of the embodiments 1-27, wherein the base plate contains less than two laminated layers.
[0189] Embodiment 29: Any of the embodiments 1-28, wherein the base plate does not contain a separate layer.
[0169]
[0190] Embodiment 30: A base plate having an upper portion and a lower portion, the base plate comprising a beryllium oxide composition containing at least 95 wt% beryllium oxide and optional fluorine / fluoride ions, the base plate demonstrating a clamping pressure of at least 133 kPa at a temperature of at least 600°C and demonstrating a decomposition change of less than 1 wt% at a temperature above 1600°C.
[0170]
[0191] Embodiment 31: The base plate demonstrates a temperature variation of less than ±3% when heated to a temperature in excess of 700° C. and / or has a temperature variation of less than 1×10 8 and / or a bulk resistivity of less than 0.016 wt %, and / or a corrosion loss of less than 0.016 wt %, and / or a dielectric constant of less than 20, and / or a surface hardness of at least 50 Rockwell on a 45N scale, and / or a coefficient of thermal expansion in the range of 5 to 15 throughout the base plate.
[0171]
[0192] Embodiment 32: The embodiment of embodiment 30 or 31, wherein the coefficient of thermal expansion varies by less than 25% from top to bottom.
[0193] Embodiment 33: Any of embodiments 30-32, wherein the base plate demonstrates a cleaning cycle time of less than 2 hours and a temperature variation of less than ±3%.
[0172]
[0194] Embodiment 34: The embodiment of any of embodiments 30-33, wherein the beryllium oxide composition comprises 1 ppb to 10 wt% ppm of magnesium oxide and 1 ppb to 10 wt% ppm of silicon dioxide.
[0173]
[0195] Embodiment 35: Any of embodiments 30-34, wherein the beryllium oxide composition comprises 1 ppb to 10 wt% ppm magnesium trisilicate.
[0196] Embodiment 36: Any of embodiments 30-35, wherein the base plate does not include a separate layer.
[0174]
[0197] Embodiment 37: Any of embodiments 30-36, wherein the base plate has a thermal conductivity gradient that decreases from top to bottom, and / or a resistivity gradient that decreases from top to bottom, and / or a purity gradient that decreases from top to bottom, and / or a theoretical density gradient that decreases from top to bottom, and / or a dielectric constant gradient that increases from top to bottom.
[0175]
[0198] Embodiment 38: Any of the embodiments of embodiments 30-37, further comprising a heating element, optionally a coiled and / or crimped heating element.
[0199] Embodiment 39: Any of embodiments 30 to 38, further comprising an antenna.
[0176]
[0200] Embodiment 40: The embodiment of any of embodiments 30-39, wherein the heating element and / or antenna comprises niobium and / or platinum.
[0201] Embodiment 41: A base plate having an upper portion and a lower portion and comprising a beryllium oxide composition, the base plate having a decreasing thermal conductivity gradient from the top to the bottom, and / or a decreasing resistivity gradient from the top to the bottom, and / or a decreasing purity gradient from the top to the bottom, and / or a decreasing theoretical density from the top to the bottom, and / or an increasing dielectric constant gradient from the top to the bottom.
[0177]
[0202] Embodiment 42: An embodiment of embodiment 41, wherein the upper thermal conductivity is in the range of 125 to 400 W / mK and the lower thermal conductivity is in the range of 146 to 218 W / mK when measured at room temperature, and / or the upper thermal conductivity is in the range of 25 W / mK to 105 W / mK and the lower thermal conductivity is in the range of 1 W / mK to 21 W / mK when measured at 800°C.
[0178]
[0203] Embodiment 43: The embodiment of embodiment 41 or 42, wherein the upper thermal conductivity is at least 6% higher than the lower thermal conductivity when measured at room temperature and / or the upper thermal conductivity is at least 6% higher than the lower thermal conductivity when measured at 800°C.
[0179]
[0204] Embodiment 44: Any of embodiments 41-43, wherein the top purity is in the range of 99.0 to 99.9 and the bottom purity is in the range of 95.0 to 99.5.
[0205] Embodiment 45: The embodiment of any of embodiments 41-44, wherein the top purity is at least 0.4% higher than the bottom purity.
[0180]
[0206] Embodiment 46: Any of embodiments 41-45, wherein the top theoretical density is in the range of 93% to 100% and the bottom theoretical density is in the range of 93% to 100%.
[0207] Embodiment 47: Any of embodiments 41-46, wherein the upper theoretical density is at least 0.5% higher than the lower theoretical density.
[0181]
[0208] Embodiment 48: Any of embodiments 41-47, wherein the upper dielectric constant is in the range of 1-20 and the lower dielectric constant is in the range of 1-20.
[0209] Embodiment 49: Any of embodiments 41 to 48, wherein the base plate does not include a separate layer.
[0182]
[0210] Embodiment 50: Any of embodiments 41-49, wherein the base plate demonstrates a clamping pressure of at least 133 KPa.
[0211] Embodiment 51: Any of embodiments 41-50, wherein the base plate demonstrates a temperature variation of less than ±3% when heated to a temperature above 700° C.
[0183]
[0212] Embodiment 52: Any of embodiments 41-51, wherein the base plate demonstrates a corrosion loss of less than 0.016 wt%.
[0213] Embodiment 53: A shaft for a pedestal assembly comprising a beryllium oxide composition containing beryllium oxide and fluorine / fluoride ions, the beryllium oxide composition having an average grain boundary or amorphous grain structure of greater than 0.1 microns.
[0184]
[0214] Embodiment 54: The embodiment of embodiment 53, wherein the beryllium oxide composition has an average particle size of less than 100 microns.
[0215] Embodiment 55: The embodiment of embodiment 53 or 54, wherein the beryllium oxide composition comprises less than 75 wt.% aluminum nitride.
[0185]
[0216] Embodiment 56: The embodiment of any of embodiments 53-55, wherein the first beryllium oxide composition has a thermal conductivity of less than 300 W / mK at room temperature.
[0217] Embodiment 57: The embodiment of any of embodiments 53-56, wherein the beryllium oxide composition has a theoretical density in the range of 90-100.
[0186]
[0218] Embodiment 58: Any of embodiments 53 to 57, wherein the upper thermal conductivity is in the range of 146 W / mK to 218 W / mK and the lower thermal conductivity is in the range of 1 W / mK to 218 W / mK when measured at room temperature, and / or the upper thermal conductivity is in the range of 1 W / mK to 21 W / mK and the lower thermal conductivity is in the range of 1 W / mK to 21 W / mK when measured at 800°C.
[0187]
[0219] Embodiment 59: Any of embodiments 53-58, wherein the upper theoretical density is at least 0.5% higher than the lower theoretical density.
[0220] Embodiment 60: Any of embodiments 53-59, wherein the first beryllium oxide composition comprises from 1 ppb to 1000 ppm of fluorine / fluoride ions.
[0188]
[0221] Embodiment 61: The embodiment of any of embodiments 53-60, wherein the first beryllium oxide composition further comprises less than 50 wt.% magnesium oxide and less than 50 wt.% ppm silicon dioxide.
[0189]
[0222] Embodiment 62: Any of embodiments 53-61, wherein the first beryllium oxide composition further comprises 1 ppb to 50 wt% ppm of alumina, 1 ppb to 10,000 ppm of sulfite, and / or 1 ppb to 1 wt% ppm of boron, barium, sulfur, or lithium, or a combination thereof (including an oxide, alloy, complex, or allotrope, or a combination thereof).
[0190]
[0223] Embodiment 63: A pedestal assembly including a shaft of any of embodiments 53 to 62, a base plate optionally containing multiple layers joined together with a brazing material, and an optional printed heating element.
[0191]
[0224]
[0046] Embodiment 64. A base plate having an upper portion and a lower portion, comprising a ceramic composition, the base plate having a clamping pressure of at least 133 kPa, a temperature variation of less than ±3% when heated to a temperature above 700°C, and / or a temperature variation of less than 1×10 at 800°C.8 A base plate demonstrating a bulk resistivity of greater than 0.016 wt%, and / or a corrosion loss of less than 0.016 wt%, and / or a dielectric constant of less than 20, and / or a surface hardness of at least 50 Rockwell on a 45 N scale, and / or a coefficient of thermal expansion in the range of 5 to 15 throughout the base plate.
[0192]
[0225] Embodiment 65: A method of manufacturing a base plate, the method comprising the steps of: providing a first BeO powder and a third BeO powder; forming a second powder from the first and third powders; forming a first (lower) region from the first powder; forming a second (middle) region from the second powder; and forming a third (upper) region from the third powder to form a base plate precursor, wherein the second region is disposed between the first and third regions; and firing the base plate precursor to form a base plate.
[0193]
[0226] Embodiment 66: The embodiment of embodiment 65, wherein the first and third (and second) powders comprise different grades of raw BeO.
[0227] Embodiment 67: The embodiment of embodiment 65 or 66, further comprising placing the heating element in an area and / or crimping the ends.
[0194]
[0228] Embodiment 68: Any of embodiments 65-67, further comprising mixing a base plate precursor to bind the powder.
[0229] Embodiment 69: Any of embodiments 65-68, further comprising cold forming the base plate precursor.
[0195]
[0230] Embodiment 70: A method of manufacturing a pedestal shaft, comprising processing a beryllium oxide composition to achieve a fluorine / fluoride ion concentration in the range of 1 ppb to 1000 ppm fluorine / fluoride ions.
[0196]
[0231] Embodiment 71: A method for cleaning a contaminated pedestal assembly, comprising the steps of providing a pedestal assembly and a wafer with the wafer placed on top of the pedestal assembly, heating the wafer to a temperature greater than 600°C, cooling the wafer to a cooling temperature in the range of less than 100°C (or not cooling at all), cleaning the plate at the cooling temperature, and optionally reheating the wafer to 600°C, wherein the cleaning cycle time from the cooling step to the reheating step is less than 2 hours.
[0197]
[0232] Embodiment 72: The embodiment of embodiment 71, wherein the cleaning cycle time is in the range of 0 to 10 minutes.
[0233] Embodiment 73: A base plate having an upper portion and a lower portion, the base plate comprising a beryllium oxide composition containing at least 95 wt% beryllium oxide and optional fluorine / fluoride ions, the base plate being capable of withstanding a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and a clamping strength of 1×10 at 800° C. 5 Base plate demonstrating bulk resistivity in excess of ohm m.
[0198]
[0234] Embodiment 74: The embodiment of embodiment 73, wherein the base plate demonstrates a temperature variation of less than ±3% when heated to temperatures above 700°C, and / or a decomposition change of less than 1 wt% at temperatures above 1600°C, and / or a dielectric constant of less than 20, and / or a surface hardness of at least 50 Rockwell on a 45N scale, and / or a coefficient of thermal expansion in the range of 5 to 15 throughout the base plate.
[0199]
[0235] Embodiment 75: The embodiment of embodiment 73 or 74, wherein the base plate comprises a beryllium oxide composition comprising 1 ppm to 5 wt% ppm magnesium oxide and 1 ppm to 5 wt% silicon dioxide and less than 1 ppb to 5 wt% ppm magnesium trisilicate.
[0200]
[0236] Embodiment 76: Any of embodiments 73-75, wherein the coefficient of thermal expansion varies less than 25% from top to bottom.
[0237] Embodiment 77: Any of embodiments 73-76, wherein the base plate demonstrates a corrosion loss of less than 0.016 wt%.
[0201]
[0238] Embodiment 78: Any of embodiments 73-77, wherein the base plate demonstrates a cleaning cycle time of less than 2 hours and a temperature variation of less than ±3%.
[0239] Embodiment 79: Any of embodiments 73 to 78, wherein the base plate does not include a separate layer.
[0202]
[0240] Embodiment 80: Any of embodiments 73-79, wherein the base plate demonstrates a temperature variation of less than ±3% when heated to a temperature above 700° C.
[0241] Embodiment 81: Any of embodiments 73-80, wherein the base plate has a thermal conductivity gradient that decreases from top to bottom, a resistivity gradient that decreases from top to bottom, and a purity gradient that decreases from top to bottom.
[0203]
[0242] Embodiment 82: The embodiment of any of embodiments 73-81, wherein the top purity is at least 0.4% higher than the bottom purity.
[0243] Embodiment 83: A pedestal assembly comprising: a shaft containing a first beryllium oxide composition containing beryllium oxide and fluorine / fluoride ions; and a base plate containing a second beryllium oxide composition containing at least 95 wt.% beryllium oxide, wherein the base plate is resistant to a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and a thermal expansion coefficient of 1×10 at 800° C. 5 A pedestal assembly demonstrating bulk resistivity of greater than ohm m.
[0204]
[0244] Embodiment 84: The embodiment of embodiment 83, wherein the first beryllium oxide composition has an average grain boundary greater than 0.1 microns.
[0245] Embodiment 85: The embodiment of embodiment 83 or 84, wherein the first beryllium oxide composition has an average particle size of less than 100 microns.
[0205]
[0246] Embodiment 86: The embodiment of any of embodiments 83-85, wherein the first beryllium oxide composition comprises from 10 ppb to 800 ppm of fluorine / fluoride ions.
[0247] Embodiment 87: The embodiment of any of embodiments 83-86, wherein the first beryllium oxide composition comprises more fluorine / fluoride ions than the second beryllium oxide composition.
[0206]
[0248] Embodiment 88: Any of embodiments 83-87, wherein the first beryllium oxide composition further comprises 1 ppb to 50 wt% ppm alumina, 1 ppb to 10,000 ppm sulfite, and / or 1 ppb to 1 wt% ppm boron, barium, sulfur, or lithium, or a combination thereof (including an oxide, alloy, complex, or allotrope, or a combination thereof).
[0207]
[0249] Embodiment 89: Any of embodiments 83-88, wherein the first beryllium oxide composition comprises less than 75 wt.% aluminum nitride and the second beryllium oxide composition comprises less than 5 wt.% aluminum nitride.
[0208]
[0250] Embodiment 90: A shaft for a pedestal assembly comprising a beryllium oxide composition containing beryllium oxide and 10 ppb to 800 ppm of fluorine / fluoride ions, wherein the beryllium oxide composition has an average grain boundary or amorphous grain structure greater than 0.1 microns and an average grain size less than 100 microns.
[0209]
[0251] Embodiment 91: A method of manufacturing a base plate, the method comprising the steps of: providing a first BeO powder and a third BeO powder; forming a second powder from the first and third powders; forming a first (lower) region from the first powder; forming a second (middle) region from the second powder; and forming a third (upper) region from the third powder to form a base plate precursor, wherein the second region is disposed between the first and third regions; and firing the base plate precursor to form a base plate.
[0210]
[0252] Embodiment 92: The embodiment of embodiment 91, wherein the first and third, and optional second powders comprise different grades of raw BeO.
[0253] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be readily apparent to those skilled in the art. In view of the above description, the relevant knowledge in the art and the above references are incorporated herein by reference in their entirety in connection with the disclosure of the "Background" and "Description of the Preferred Embodiments". In addition, the aspects of the present invention and parts of the various embodiments and various features within the following and / or appended claims may be combined or exchanged in whole or in part. In the above description of various embodiments, an embodiment that refers to another embodiment may be combined with other embodiments as appropriate, as will be understood by those skilled in the art. Furthermore, those skilled in the art will appreciate that the above description is illustrative only and is not intended to be limiting. Specific embodiments of the present invention are as follows. [Aspect 1] 1. A base plate having an upper portion and a lower portion, the base plate comprising a beryllium oxide composition containing at least 95 wt. % beryllium oxide and optional fluorine / fluoride ions, the base plate having a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and a clamping strength of 1×10 5 Base plate demonstrating bulk resistivity in excess of ohm m. [Aspect 2] 2. The base plate of embodiment 1, wherein the base plate comprises a beryllium oxide composition comprising 1 ppm to 5 wt% ppm magnesium oxide and 1 ppm to 5 wt% silicon dioxide and 1 ppm or more and less than 5 wt% ppm magnesium trisilicate. [Aspect 3] The base plate is Temperature fluctuations of less than ±3% when heated to temperatures above 700°C, and / or Decomposition changes of less than 1 wt % at temperatures above 1600°C, and / or A dielectric constant less than 20, and / or A surface hardness of at least 50 Rockwell on the 45N scale, and / or A thermal expansion coefficient in the range of 5 to 15 throughout said base plate 2. The base plate of embodiment 1, [Aspect 4] 2. The base plate of embodiment 1, wherein the coefficient of thermal expansion varies by less than 25% from top to bottom. [Aspect 5] 2. The base plate of embodiment 1, wherein the base plate demonstrates a corrosion loss of less than 0.016 wt.%. [Aspect 6] 2. The baseplate of embodiment 1, wherein the baseplate demonstrates a cleaning cycle time of less than 2 hours and a temperature variation of less than ±3%. [Aspect 7] 2. The base plate of embodiment 1, wherein the base plate does not include a separate layer. [Aspect 8] 2. The base plate of embodiment 1, wherein the base plate demonstrates a temperature variation of less than ±3% when heated to a temperature greater than 700° C. [Aspect 9] 2. The base plate of embodiment 1, wherein the base plate has a decreasing thermal conductivity gradient from top to bottom, a decreasing resistivity gradient from top to bottom, and a decreasing purity gradient from top to bottom. [Aspect 10] 2. The base plate of embodiment 1, wherein the upper purity is at least 0.4% higher than the lower purity. [Aspect 11] 1. A pedestal assembly comprising: a shaft containing a first beryllium oxide composition containing beryllium oxide and fluorine / fluoride ions; a base plate containing a second beryllium oxide composition containing at least 95 wt. % beryllium oxide; Includes The base plate has a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and a clamping pressure of 1×10 5 A pedestal assembly demonstrating bulk resistivity of greater than ohm m. [Aspect 12] 12. The assembly of embodiment 11, wherein the first beryllium oxide composition has an average grain boundary greater than 0.1 microns. [Aspect 13] 12. The assembly of embodiment 11, wherein the first beryllium oxide composition has an average particle size of less than 100 microns. [Aspect 14] 12. The assembly of embodiment 11, wherein the first beryllium oxide composition comprises 10 ppb to 800 ppm of fluorine / fluoride ions. [Aspect 15] 15. The assembly of any one of embodiments 11 to 14, wherein the first beryllium oxide composition comprises more fluorine / fluoride ions than the second beryllium oxide composition. [Aspect 16] The first beryllium oxide composition comprises: Alumina from 1ppb to 50wt%ppm, Sulfites between 1ppb and 10,000ppm, and / or 1 ppb to 1 wt% ppm of boron, barium, sulfur, or lithium, or any combination thereof (including oxides, alloys, complexes, or allotropes, or any combination thereof) 12. The assembly of embodiment 11, further comprising: [Aspect 17] 12. The assembly of embodiment 11, wherein the first beryllium oxide composition comprises less than 75 wt.% aluminum nitride and the second beryllium oxide composition comprises less than 5 wt.% aluminum nitride. [Aspect 18] A shaft for a pedestal assembly comprising a beryllium oxide composition containing beryllium oxide and 10 ppb to 800 ppm of fluorine / fluoride ions, A shaft wherein said beryllium oxide composition has an average grain boundary or amorphous grain structure greater than 0.1 microns and an average grain size less than 100 microns. [Aspect 19] A method of manufacturing a base plate, comprising the steps of: providing a first BeO powder and a third BeO powder; forming a second powder from the first and third powders; forming a first (lower) region from the first powder; forming a second (middle) region from the second powder; forming a third (upper) region from the third powder to form a base plate precursor, the second region being disposed between the first and third regions; calcining the base plate precursor to form the base plate; A method comprising: [Aspect 20] 20. The method of embodiment 19, wherein the first and third and optional second powders comprise different grades of raw BeO.
Claims
1. 1. A base plate having an upper portion and a lower portion, the base plate comprising a beryllium oxide composition containing at least 95 wt. % beryllium oxide, at least 1 ppm but less than 5 wt. % magnesium trisilicate, and optional fluorine / fluoride ions, the base plate having a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and a clamping pressure of 1×10 at 800° C. 5 A base plate that demonstrates bulk resistivity in excess of ohm m.
2. 10. The base plate of claim 1, wherein the base plate comprises a beryllium oxide composition comprising 1 ppm to 5 wt. % magnesium oxide and 1 ppm to 5 wt. % silicon dioxide.
3. The base plate is Temperature fluctuations of less than ±3% when heated to temperatures above 700°C; and / or Decomposition changes of less than 1 wt % at temperatures above 1600° C., and / or a dielectric constant of less than 20, and / or A surface hardness of at least 50 Rockwell on the 45N scale, and / or A coefficient of thermal expansion ranging from 5 to 15 throughout said base plate 13. The base plate of claim 1 .
4. 10. The base plate of claim 1, wherein the coefficient of thermal expansion varies less than 25% from top to bottom.
5. 10. The base plate of claim 1, wherein the base plate demonstrates a corrosion loss of less than 0.016 wt%.
6. 10. The baseplate of claim 1, wherein the baseplate demonstrates a cleaning cycle time of less than two hours and a temperature variation of less than ±3%.
7. The base plate of claim 1 , wherein the base plate does not include a separate layer.
8. 10. The base plate of claim 1, wherein the base plate demonstrates a temperature variation of less than ±3% when heated to temperatures above 700°C.
9. 10. The base plate of claim 1, wherein the base plate has a decreasing thermal conductivity gradient from top to bottom, a decreasing resistivity gradient from top to bottom, and a decreasing purity gradient from top to bottom.
10. 2. The base plate of claim 1, wherein the upper purity is at least 0.4% greater than the lower purity.
11. 1. A pedestal assembly comprising: a shaft containing a first beryllium oxide composition containing beryllium oxide and fluorine / fluoride ions; a base plate containing a second beryllium oxide composition containing at least 95 wt. % beryllium oxide; Includes The base plate has a clamping pressure of at least 133 kPa at a temperature of at least 600° C. and a clamping force of 1×10 5 A pedestal assembly demonstrating bulk resistivity of greater than ohm m.
12. 12. The assembly of claim 11, wherein the first beryllium oxide composition has an average grain boundary greater than 0.1 microns.
13. 12. The assembly of claim 11, wherein the first beryllium oxide composition has an average particle size of less than 100 microns.
14. 12. The assembly of claim 11, wherein the first beryllium oxide composition comprises 10 ppb to 800 ppm fluorine / fluoride ions.
15. 15. The assembly of any one of claims 11 to 14, wherein the first beryllium oxide composition comprises more fluorine / fluoride ions than the second beryllium oxide composition.
16. The first beryllium oxide composition comprises: 1 ppb to 50 wt % alumina, Sulfites from 1 ppb to 10,000 ppm, and / or 1 ppb to 1 wt % of boron, barium, sulfur, or lithium, or a combination thereof (including oxides, alloys, complexes, or allotropes, or a combination thereof) The assembly of claim 11 further comprising:
17. 12. The assembly of claim 11, wherein the first beryllium oxide composition comprises less than 75 wt.% aluminum nitride and the second beryllium oxide composition comprises less than 5 wt.% aluminum nitride.
18. A shaft for a pedestal assembly comprising a beryllium oxide composition containing beryllium oxide and 10 ppb to 800 ppm fluorine / fluoride ions, A shaft wherein said beryllium oxide composition has an average grain boundary or amorphous grain structure greater than 0.1 microns and an average grain size less than 100 microns.
19. A method of manufacturing a base plate, comprising the steps of: providing a first BeO powder and a third BeO powder; forming a second powder from the first and third powders; forming a first (lower) region from the first powder; forming a second (middle) region from the second powder; forming a third (upper) region from the third powder to form a base plate precursor, the second region being disposed between the first and third regions; calcining the base plate precursor to form the base plate; A method comprising:
20. 20. The method of claim 19, wherein the first, third and optional second powders comprise different grades of raw BeO.
Citation Information
Patent Citations
Semiconductor manufacturing device and manufacturing method
JP1997045756A
Negatively charged atom generator
JP2003172798A
Plasma processing apparatus and manufacturing method of semiconductor device
JP2005116645A
Ceramic cover wafer of aluminum nitride or beryllium oxide
JP2009132991A
Semiconductor processing equipment with high temperature resistant nickel alloy joints and method of manufacturing the same
JP2021504287A